From target identification to intervention: Tackling microbial contamination challenges in cultivated meat production using antimicrobial peptides - Zejia Lin; Yuan Guo; Dini Deng; Xianzhe Li; Emma Y.H. Koay; Mario P.S. Chin; Carrie K.Y. Chan; Dan Li (Food Microbiology, 2026)

Distinct regulatory elements of SLC6A14 expression contribute to modification of cystic fibrosis phenotypes - Mohsen Esmaeili; Cheng Wang; Fan Lin; Naim Panjwani; Adele Chan; Gengming He; Katherine Keenan; Julie Avolio; Ann Harris; Johanna M. Rommens; Lisa J. Strug (Human Genetics, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Mechanistic insights into the migration and transformation of As2O3 by HCl during simulated MSW incineration flue gas cooling - Shuai Li; Hongyun Hu; Peixiong Tan; Chan Zou; Yongda Huang; Yipeng Wang; Zhong Lin; Hong Yao (Fuel, 2026)

Non-destructive computer vision grading of Jin-Huang mango using texture and surface-blemish cues for packing-line quality control - Yung-Kuan Chan; Zih-Yan Ciou; Yu-Yi Chen; Chuen-Horng Lin; Jiunn-Lin Wu; Huan-Yu Chen (Journal of Food Engineering, 2026)

Nonlinear structural reorganisation of corn starch induced by high-pressure processing regulates its thermal, pasting and hydration behaviour - Wen-Chien Lu; Yung-Jia Chan; Ching-Jung Lin; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Autocatalytic DNA nanosphere assembly activated by endogenous APE1 for intracellular miR-21 imaging - Liuting Mo; Chunfen Zhang; Rongzheng Yuan; Yan Hong; Chan Yang; Weiying Lin (Analytica Chimica Acta, 2026)

Exploring the mechanism of platycodon grandiflorum saponins in treating Mycoplasma pneumoniae pneumonia based on intestinal microbiota and metabolomics - Rui Shuang Ji; Yun Fei Yang; Chan Yu Wu; Zhen Jing Yang; Jin Zhao Du; Jing Huang Fu; Lin Yao; Wei Ming Wang (Food Bioscience, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Combined exposure to hypoxia and 17α-ethinylestradiol alters reproductive traits in marine medaka - Xian Qin; Jiezhang Mo; Huiju Lin; Yi Yang; Emily Sze Wan Wong; Min Pan; Sidney Man Ngai Chan; Rudolf Shiu Sun Wu; William Ka Fai Tse; Keng Po Lai (Aquatic Toxicology, 2026)

Neighbourhood-scale estimation of air temperature in complex urban areas using a multistep machine learning-based data fusion approach - Naveed Ahmad; Kimberly Tasha Jiayi Tang; Jimmy W.M. Chan; Changqing Lin (Urban Climate, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Matriptase proteolysis selectively drives disassembly and internalization of the claudin-7 complex while preserving E-cadherin - Yu-Ling A. Kao; He-Yu Huang; Yin S. Yu; Nanxi Huang; Ya-Chin Chan; Chen-Ray Lee; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2026)

The chlorination mechanism of arsenic during the arsenopyrite decomposition: experimental and theoretical study - Chan Zou; Rui Liang; Huimin Liu; Zhong Lin; Chunbo Wang (Waste Disposal & Sustainable Energy, 2026)

The learning efficiency of the ant Anoplolepis gracilipes (Hymenoptera: Formicidae) varies with temperature - C.-H. Chan; T.-S. Lin; H.-D. Lin; C.-I. Chiu (Insectes Sociaux, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Protective effects of sodium benzoate against toluene-induced reward enhancement, behavioral disturbances, and impaired synaptic plasticity in mice - Chung-Pin Hsieh; Mei-Yi Lee; Chia-Yu Lin; Ming-Huan Chan; Hwei-Hsien Chen (NeuroToxicology, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Cellular vesicle–electrically conducting polymer integrating with microalgae attenuate retinal inflammation associated with IL-6, immunomodulation, and pro-inflammatory cytokines in diabetes-related retinal disease - Andrew E.-Y. Chuang; Yo-Lin Chen; Chia-Hung Liu; Hieu Trung Nguyen; Tsung-Jen Wang; I-Chan Lin (Chemical Engineering Journal, 2026)

TEDD 2.0: an advanced temporal gene expression database enabled by in-silico functional analyses for developmental mechanism investigation - Chi Chun Chan; King Kin Lam; Lin Chen; Mingyang Yu; Jingwen Hu; Yujie Zhu; Yuting Zheng; Jia Zheng; Kwong Wai Choy; Zirui Dong (Science China Life Sciences, 2026)

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

Improving consistency of WRF-UCM-based typhoon wind field simulations with field observations: A sensitivity analysis of model parameters - Yuxin Zhang; Qiusheng Li; Shuyang Cao; Junyi He; P.W. Chan; Lin Zhao; Jinxin Cao (Urban Climate, 2026)

Cadmium exposure is associated with impaired ovarian function: Potential role of cadmium-induced ferroptosis in granulosa cells - Jing Li; Yutong Wang; Yali Huang; Nidong Li; Yingxin Zhu; Shengli Lin; Linlin Wang; Wei Guo; Lailai Yan; Chan Tian; Ying Wang (Journal of Hazardous Materials, 2026)

Effect of oxygen-containing functional groups on selenium removal by the carbonaceous adsorbent from MSW incineration flue gas - Shuaijie Yu; Shuai Li; Hongyun Hu; Linxia Gao; Zhong Lin; Chan Zou; Lu Dong; Yongda Huang; Hong Yao (Fuel, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

An R2R3-MYB transcription factor TgMYB44 positively regulates petal senescence by enhancing ABA biosynthesis in tulip - Haipo Yang; Yikun Wu; Chengxiao Yuan; Hongqing Yin; Lin Xiang; Xuewei Wu; Honglin Deng; Bo Sun; Zhulong Chan; Yanping Wang (Plant Cell Reports, 2026)

Blood flow restriction modulates common drive to motor units and force precision: implications for neuromuscular coordination - Chia-Chan Wu; Yen-Ting Lin; Yueh Chen; Yi-Ching Chen; Ing-Shiou Hwang (European Journal of Applied Physiology, 2026)

Pulsed electric fields as a green alternative to chemical treatment: Toward enhanced molecular interactions and performance in biodegradable preservation films - Rui Wang; Pei-Feng Guo; Ying Xu; Xing-Chan Xie; Dan-Dan Lin; Yu-Wei Wu; Dong-Yang Xu; Lang-Hong Wang; Xin-An Zeng (Chemical Engineering Journal, 2026)

Revisiting the Anti-Drug Antibody Assay Drug Tolerance of a Commercial Biological Product - James Zanghi; Nancy Yu; Benjamin T. Andrews; Phyllis Chan; Maxime Usdin; Cecilia Chiu; WeiYu Lin; Alyse Lin; Yuan Song (The AAPS Journal, 2025)
Drug tolerance (DT) is a critical attribute of anti-drug antibody (ADA) assays for assessing clinical immunogenicity. We present a unique situation where a previously approved commercial product, atezolizumab, required re-assessment of the assay DT to meet an increased drug exposure demand arising from a new route of administration (subcutaneous) and align with updated health authority (HA) regulations. Rather than redevelop the existing ADA assay, which could disrupt ongoing clinical trials, we identified a new anti-idiotype (anti-ID) antibody surrogate that demonstrated that the assay maintained adequate DT for the new route of administration. This streamlined approach addressed concerns regarding higher serum trough concentrations with subcutaneous administration and stricter sensitivity expectations. We established a target DT concentration based on population pharmacokinetic modeling to ensure adequate ADA characterization at steady state. This case study highlights the value of having alternative surrogate ADAs and demonstrates that achieving stringent DT requirements can be accomplished without extensive method redevelopment. We also introduce the broader implications of surrogate ADA selection, binding kinetics, and the clinical relevance of achieving high DT in the context of atezolizumab's efficacy and safety profile. This work also emphasizes the importance of considering bioanalytical assay characteristics, such as DT, throughout a product’s lifecycle. Graphical Abstract

Fluoride removal by MgO-based adsorbents synthesized via distinct routes: Comparative evaluation of adsorption efficiency and column-scale stability - Yee-Rui Chan; Wei-Han Lin; Wei-Zhe Lin; Rao Y. Surampalli; Ying-Liang Yu; Chih-Ming Kao (Journal of Water Process Engineering, 2025)

Simultaneous quantification of fructose and sucrose in beverages using microfluidic paper chip and colorimetric pixel-area analysis method - Chan-Chiung Liu; To-Lin Chen; Hsing-Meng Wang; Kuan-Hsun Huang; Lung-Ming Fu (Food Chemistry, 2025)

Editorial Expression of Concern: Expression of bioactive human interferon-gamma in transgenic rice cell suspension cultures - Tzy-Li Chen; Yi-Ling Lin; Yi-Ling Lee; Ning-Sun Yang; Ming-Tsair Chan (Transgenic Research, 2025)

Downlisting and recovery of species assessed by the IUCN - Mu‐Ming Lin; Richard A. Fuller; In‐Ki Kwon; Kisup Lee; Simba Chan; Wangwang Qiu; Yat‐Tung Yu; Chi‐Yeung Choi (Conservation Biology, 2025)
Despite the increasing number of species assessed for extinction risk by the International Union for Conservation of Nature (IUCN) (163,040 species as of 2024), only about 1 in 1,000 have been downlisted due to genuine population improvement. Although this rare conservation achievement has been widely celebrated in several recent cases, some other downlisting decisions have met with controversy. A primary role of the IUCN is to assess extinction risk. In this role, it must maintain its independence and not be influenced by the public outcry that may occur when a high‐profile species is downlisted, even if well‐established conservation programs may be disrupted or abandoned as a result. We explored the potential positive and negative consequences of downlisting for conservation efforts through case studies of the giant panda ( Ailuropoda melanoleuca ), red‐crowned crane ( Grus japonensis ), saiga antelope ( Saiga tatarica ), and black‐faced spoonbill ( Platalea minor ), which has recently been proposed for downlisting. Although downlisting can enable more effective use of limited resources, these cases highlight potential risks, including weakened legal backing, diversion of resources away from the species, and declining public and political support. The relatively unquestioned downlisting of the saiga antelope illustrates how early and inclusive engagement of local experts, assessors, donors, and other stakeholders can help ensure that decisions are effectively communicated and implemented without jeopardizing species recovery. The IUCN Green Status of Species assessment is a complementary tool to the IUCN Red List and offers a useful measure of conservation progress, which can help decision makers ensure that downlisting does not undermine long‐term conservation efforts.

Seismic behavior of innovative precast hybrid steel-concrete beam-column connections - Chien-Chung Chen; Hung-Jen Lee; Yi-Yao Zhao; Yin-Nan Huang; Chiu-Huang Lin; Hsiao-Wei Chan (Engineering Structures, 2025)

Traversing the Valley of Death for nanotechnology-based natural products: strategies and insights from pharmaceutical stakeholders - Jian Sheng Loh; Chan Yew Low; Wei Peng Low; Yun Lin Ng; Wen Qi Mak; Li Kar Stella Tan; Hong Hao Chan; Yong Sze Ong; Stephanie Kay Ann Cheah; Emmellie Laura Albert; Chee Wun How (Drug Delivery and Translational Research, 2025)

Demystifying priority of deploying sustainable petrochemical waste management: Multi-Stakeholder insights from a developing country - Mei Kuen Wang; Juin Yau Lim; ZiYu Lin; Sue Lin Ngan; Yi Jing Chan; Hon Loong Lam (Journal of Cleaner Production, 2025)

Contrasting short-term dynamics of supraglacial ponds along the Hindu Kush-Himalaya revealed by PlanetScope imagery and deep learning - Xingyu Xu; Lin Liu; Lingcao Huang; Yan Hu; Guoqing Zhang; Adina Racoviteanu; Emily Victoria Liu; YingTo Agnes Chan (Global and Planetary Change, 2025)

Bioavailability, absorption, digestion and metabolism of natural hydroxycinnamic acids in gastrointestinal tract - Yi Lin Chan; Lee Suan Chua; Zanariah Binti Hashim (Food Bioscience, 2025)

Simultaneous carrier concentration regulation and grain boundary passivation enable over 14 % efficient Ag-alloyed kesterite solar cells - Mengyang Wang; Yu Mao; Wenjian Chan; Yuanyuan Huang; Yanmei Deng; Ziyang Ren; Ening Gu; Xianzhong Lin; Guowei Yang (Chemical Engineering Journal, 2025)

Microemulsion-assisted synthesis of Mn-TCPP@MnxOy heterostructures for enhanced photodynamic therapy via O2 self-production and GSH-activatable imaging - Chan Yang; Yanling Zhao; Yanru Qin; Zihan Yan; Ziyi He; Nan Yang; Liuting Mo; Weiying Lin (Chemical Engineering Journal, 2025)

Combination of Large Language Model and Retrieval-augmented Generation for Inference of Traditional Chinese Medicine Prescriptions and Syndrome Differentiations: A Study on Sleeping Disorders - PoYu Huang; ChihNung Wang; ShaoHung Lu; YaChuan Chan; ZhiLiang Chen; WenChen Lin; Jung-Peng Chiu; YungHsin Chen (Journal of Medical and Biological Engineering, 2025)
Propose The objective of this study was to combine a large language model (LLM) with retrieval-augmented generation (RAG) to develop a tool for syndrome type determination and a medical prescription inference model for sleep disorders in a generative artificial-intelligence-based traditional Chinese medicine (TCM) system. The tool uses the disease-formula-syndrome inference framework in TCM to map various combinations of prescription formulas and syndromes. Methods This study selected 6,747 cases of sleep disorders along with their single- and compound-herb formula prescriptions (finished herbal products) to construct the RAG knowledge base. A RAG-based LLM was then employed to generate medical prescription formulas corresponding to syndrome types, as well as for reverse generation and validation. Results The results demonstrate that the RAG-based LLM can determine TCM syndrome types that align closely with clinical reality. Moreover, it can consistently provide comprehensive syndrome mappings for various combinations of prescription formulas. However, limitations were observed in a few instances where only single herbs were identified and compound-herb formulas were either omitted or incorrect, resulting in significantly lower scores. Conclusion The results indicate that the proposed method can enhance learning efficiency in TCM diagnostics and support clinical diagnosis and the RAG-based LLM need to be improved to provide comprehensive responses. Future efforts could focus on expanding the dataset and optimizing the LLM to enhance accuracy and reliability.

Investigating the role of top-down regulation and bottom-up cues in eating styles transitions: a one-year cohort study with young adults - Meijun Chen; Jiehu Yuan; Yucan Xu; Wendy Wing Tak Lam; Lin Yang; Derwin King Chung Chan; Qiuyan Liao (Appetite, 2025)

The correlation of immunotoxicity with size and chemical properties of particulate matter within macrophages - Hsiang-Yu Kung; Yi-Shiuan Wang; Yung-Jui Chen; Ting-Hsuan Wu; Jai-Yu Chen; Yueh-Feng Wen; Yu-Cheng Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Macrophage-targeted lipid nanoparticles based on Dendron-like lipids deliver mTOR inhibitor to alleviate systemic lupus erythematosus - Keqian Du; Guantao He; Fujian Huang; Xi Zhang; Xiaohan Zhang; Junjin Jie; Chan Huang; Yuqiong Wu; Huiyang Fan; Zhiming Lin; Lin-Ping Wu (Chemical Engineering Journal, 2025)

Modification effects of socioeconomic, demographic, and geographic factors on the association between temperature and cause-specific mental disorders among Taiwanese population - Gerry Andhikaputra; Li-Wen Deng; Hsi-Yu Hsiao; Yu-Kai Lin; Ta-Chien Chan; Hsuan-Fu Chao; Yu-Chun Wang (International Journal of Biometeorology, 2025)

Estimation of Dynamic Characteristic Parameters for Long-Lived Tropical Cyclone Freddy (2023) from Active/Passive Spaceborne Microwave Sensors - He Fang; William Perrie; Lin Chen; Hui Su; Pakwai Chan; Guosheng Zhang (Advances in Atmospheric Sciences, 2025)

Speciation of coral-associated barnacles: generalists versus specialists in the Indo-West Pacific - Hsiu-Chin Lin; Lorenzo C. Halasan; Yoko Nozawa; Benny K. K. Chan (Coral Reefs, 2025)

Electrocatalytic oxidation of bisphenol A using optimized Fe/Cu cathodic catalysts: Biotoxicity and microbial community analysis in bioelectro-Fenton systems - Shu-Hui Liu; Chang-Ting Hsieh; Chi-Wen Lin; Yen San Chan (International Biodeterioration & Biodegradation, 2025)

Investigating the pyrolysis of large biomass particle streams in CO2/H2O atmosphere at high heating rates: A modeling approach - Jiaye Zhang; Xiangdong Li; Hui Lin; Stephan Heberlein; Wei Ping Chan; Xuebin Wang; Houzhang Tan; Grzegorz Lisak (Fuel, 2025)

Copper doped carbon dots for selective determination of regulated aniline additives and safe hair dyeing - Zhanghong Guo; Lin Zhou; Liping Zhang; Haining Cui; Jinxin Ma; Chan Wang; Qijun Song (Analytica Chimica Acta, 2025)

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

Microbiological Activity and Oxygen Availability Influence Arsenic Mobilization and Redox Transformation in an Arsenic-Rich Aquifer - Yu-Chen Su; Yu-Ju Chu; Chia-Cheng Wei; Chan-Wei Yu; Pei-Ling Yen; Yu-Hsuan Kuo; Ting-An Lin; Vivian Hsiu-Chuan Liao (Exposure and Health, 2025)

Isotopic Analysis for Tracing Vertical Growth Trajectories of Hailstones - Xiangyu Lin; Haifan Zhang; Xiaofei Li; Qinghong Zhang; Andrew Heymsfield; Kai Bi; Chan-Pang Ng; Chong Wu; Dianli Gong (Advances in Atmospheric Sciences, 2025)

Monitoring of genetically modified crops in food products in Singapore - Yanwen Wang; Kung Ju Lin; Emily Huey Shyan Teo; Yong Quan Tan; Yuansheng Wu; Kern Rei Chng; Joanne Sheot Harn Chan; Li Kiang Tan (Food Control, 2025)

Methamphetamine and HIV-1 Tat Protein Synergistically Induce Endoplasmic Reticulum Stress to Promote TRIM13-Mediated Neuronal Autophagy - Chan Wang; Genmeng Yang; Jian Huang; Yunqing Tian; Chi-Kwan Leung; Lin Miao; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Liu Liu; Juan Li; et al. (Molecular Neurobiology, 2025)

Optimizing the generated waste proportion to improve the characteristics of biochar for CO2 sequestration and other applications - Baala H. Anandapadmanaban; Yen San Chan; Chi-Wen Lin; Shu-Hui Liu (Environment, Development and Sustainability, 2025)

The Role and Mechanism of TRIM13 Regulation of TRAF6 Ubiquitination in the Synergy of Inflammatory Responses and Neurotoxicity Induced by METH and HIV- 1 Tat Protein in Astrocytes - Yi Tan; Lin Miao; Chan Wang; Haowei Wang; Yi Li; Yizhen Huang; Hanxin Teng; Yunqing Tian; Genmeng Yang; Xiaofeng Zeng; Juan Li (Neurotoxicity Research, 2025)

Collection of stomatopod larvae unveiled the existence of an undescribed genus in Lysiosquillidae around Japanese waters - Koshi Fujita; Chia-Wei Lin; Kingsley J. H. Wong; Mikio Kato; Tin-Yam Chan; Kaori Wakabayashi (Marine Biodiversity, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

Role of Exercise on Neuropathic Pain in Preclinical Models: Perspectives for Neuroglia - Chen-Chen Zhu; Yi-Li Zheng; Chan Gong; Bing-Lin Chen; Jia-Bao Guo (Molecular Neurobiology, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Association between low-dose ionizing radiation and hypertension: a cohort study in China - Beining Wu; Lin Song; Lan Lin; Jin Wang; Lejia Zhu; Weiling Chan; Geyang Li; Li Zhou; Zhongying Xu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2025)

Facile and enlargeable preparation of piezocatalytic CaCO3 for efficient degradation of organic dyes - Yunong Zhao; Lin Zhou; Dongliang Xiang; Zhanghong Guo; Chan Wang; Qijun Song (Environmental Research, 2025)

Conjugated polymer of Multi-arm-PEG and dimethylsiloxane (CPMD) for the effective transdermal delivery of deoxycholic acid for fat reduction - Hwajun Jeong; Hye-Lin Kim; Harim Kim; Min-Suk Lee; Jae-Min Cho; Chan Lee Park; Hyo In Kim; Jinbong Park; Dokyoung Kim (Chemical Engineering Journal, 2025)

Parental stress and environmental influences on children's physician-diagnosed food allergy - Chan Lu; Ying Jiang; Lin Wang; Mengju Lan; Faming Wang (Building and Environment, 2025)

Early-life exposure to outdoor temperature and the risk of childhood allergic diseases: A multicentre retrospective cohort study - Faming Wang; Lin Wang; Ying Jiang; Mengju Lan; Wenhui Yang; Zijing Liu; Chan Lu (Building and Environment, 2025)

Changes in the small-molecule fingerprints of rice planted near an industrial explosion site in Taiwan - Wen-Ling Chen; Husan-Yu Tai; Chang-Chuan Chan; Hung-Chien Lin; Ting-Hsuan Hung; Mong-Hsun Tsai; Chia-Cheng Wei; Yu-San Han; Chuan-Chou Shen (Environmental Science and Pollution Research, 2024)

Quantifying the effects of the microphysical hygroscopic restructuring of soot on ensemble optical properties and satellite aerosol optical depth retrievals - Kuo-En Chang; Tang-Huang Lin; Ta-Chih Hsiao; Yi-Ling Chang; Tzu-Chi Lin; Chih-Yu Chan; Charles C.-K. Chou (Science of The Total Environment, 2024)

Exploring the geographical equity-efficiency tradeoff in cycling infrastructure planning - Madeleine Bonsma-Fisher; Bo Lin; Timothy C.Y. Chan; Shoshanna Saxe (Journal of Transport Geography, 2024)

Response to “Letter to the Editors” regarding “A nationwide case-referent study on elevated risks of adenocarcinoma lung cancer by long-term PM2.5 exposure in Taiwan since 1997” - Wei-Chi Lin; Ruei-Hao Shie; Tzu-Hsuen Yuan; Chien-Hua Tseng; Chun-Ju Chiang; Wen-Chung Lee; Chang-Chuan Chan (Environmental Research, 2024)

Di(2-ethylhexyl) phthalate disrupts circadian rhythm associated with changes in metabolites and cytochrome P450 gene expression in Caenorhabditis elegans - Pei-Ling Yen; Ting-An Lin; Chun-Han Chang; Chan-Wei Yu; Yu-Hsuan Kuo; Tzu-Ting Chang; Vivian Hsiu-Chuan Liao (Environmental Pollution, 2024)

Hydrothermal preparation of pharmaceuticals adsorbents from chitin and chitosan: Optimization and mechanism - Xin Lin; Kayee Chan; Khonekeo Kingkhambang; Hideki Hayashi; Anatoly Zinchenko (Bioresource Technology, 2024)

Parental stress interaction with environmental factors in childhood allergic asthma: Early life significance - Chan Lu; Lin Wang; Mengju Lan; Ying Jiang; Faming Wang (Building and Environment, 2024)

Auxin Receptor TRANSPORT INHIBITOR RESPONSE1 Promotes Tulip Plant Growth and Bulb Swelling - Qi Sun; Bei Zhang; Lin Xiang; Yanping Wang; Zhulong Chan (Journal of Plant Growth Regulation, 2024)

Corrigendum to ‘Estimates of the global burden of cancer-related deaths attributable to residential exposure to petrochemical industrial complexes from 2020 to 2040’ [Environ. Pollut. 350 (2024) 123955] - Hathaichon Boonhat; Yue Leon Guo; Chang-Chuan Chan; Ro-Ting Lin (Environmental Pollution, 2024)

Seismic rehabilitation of RC frames with innovative precast U-shaped UHPC jackets: Experimental evaluation and computational simulation - Chung-Chan Hung; Chin-Cheng Lin; Tuong Dat Dinh Do (Engineering Structures, 2024)

Integrating DNA logic computation and Self-Replication on nanospheres for amplified detection of Dual miRNAs - Liuting Mo; Yan Hong; Rongzheng Yuan; Mingxiu Mo; Chan Yang; Weiying Lin (Chemical Engineering Journal, 2024)

Exploring the effects of pemetrexed on drug resistance mechanisms in human lung adenocarcinoma and its association with PGRMC1 - Ssu-Yun Wu; En-Chi Liao; Yueh-Feng Wen; Yi-Shiuan Wang; Han Meng; Hsiu-Chuan Chou; Hong-Lin Chan (Chemico-Biological Interactions, 2024)

Natural shading is helpful but not sufficient for mitigating warming in green sea turtle nests in the tropical South China Sea - Tsung-Han Liu; Ming-Shiou Jeng; Chan-Yuan David Lee; Chih-Wei Tu; Po-Hsiung Lin; Chaolun Allen Chen; Chia-Ying Ko (Biological Conservation, 2024)

Prediction of parameters in the Ibarra–Medina–Krawinkler model for reinforced concrete columns using random forest and active learning - Peng-Yu Chen; Kun-Chan Lee; Tsung-Lin Li (Soil Dynamics and Earthquake Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Numerical investigation of the oxy-fuel combustion in the fluidized bed using macroscopic model supported by CFD-DDPM - Lu Dong; Liang Wang; Huaizhou Wen; Zhong Lin; Zhiyi Yao; Chan Zou; Hongpeng Xu; Hongyun Hu; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Association between concentrations of rare earth elements in chorionic villus and risk for unexplained spontaneous abortion - Meng Lin; Lailai Yan; Xiaoye Wang; Yutong Wang; Ying Zhou; Linlin Wang; Chan Tian (Environmental Research, 2024)

Practical Characterization Strategies for Comparison, Qualification, and Selection of Cell Viability Detection Methods for Cellular Therapeutic Product Development and Manufacturing - Yongyang Huang; Rachel Watkins; Samir Patel; Mackenzie Pierce; Carolina Franco Nitta; Henry Qazi; William L. Rice; Bo Lin; Chris Lowe; Carlos le Sage; Leo Li-Ying Chan (Journal of Fluorescence, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Exendin-4, a glucagon-like peptide-1 receptor agonist, alleviates muscular dysfunction and wasting in a streptozotocin-induced diabetic mouse model compared to metformin - Ding-Cheng Chan; Yuan-Cheng Lin; Huei-Ping Tzeng; Rong-Sen Yang; Meng-Tsan Chiang; Shing-Hwa Liu (Tissue and Cell, 2024)

Genotoxicity and cytotoxicity in male reproductive cells caused by sediment pollutants - Meng-Wei Lin; Jai-Yu Chen; Yu-Xuan Ye; Wei-Yi Chen; Hong-Lin Chan; Hsiu-Chuan Chou (Science of The Total Environment, 2024)

Formation of secondary aerosol by 222 nm Far-UVC irradiation on SO2 - Zhancong Liang; Liyuan Zhou; Kunpeng Chen; Ying-Hsuan Lin; Alvin C.K. Lai; Patrick K.H. Lee; Patrick H.L. Sit; Ran Yin; Chak K. Chan (Atmospheric Environment, 2024)

Interdecadal variability of winter and spring Eurasian snow depth and its impact on Eastern China precipitation - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Yumeng Liu; Hanhui Zhu (Climate Dynamics, 2024)
Empirical orthogonal function (EOF) and correlation analyses were employed to investigate the winter and spring snow depth in Eurasia and its relationship with Eastern China precipitation based on the observed and reanalyzed data from 1980 to 2016. The results show that the winter and spring snow cover in Eurasia not only highlights a decreasing trend due to global warming (the first EOF mode, its variance accounted for 24.4% and 22.6% of the total variance) but also exhibits notable interdecadal variation (the second EOF mode, its variance accounted for 10.2% and 11.5% of the total variance). The second EOF mode of winter snow depth in Eurasia is characterized by a west-east dipole pattern. It was observed that the spatial correlation pattern between the EOF2 of Eurasian snow depth and summer precipitation in China closely resembles the meridional quadrupole structure of the third EOF mode of summer precipitation in China. This pattern is characterized by excessive rainfall in Northeast China and the lower-middle reaches of the Yangtze River, and less rainfall over the Yellow River basin and southern China. The EOF mode of spring snow depth not only reflects the declining trend but also regulates precipitation in Eastern China. The possible mechanisms by which snow depth causes changes in soil moisture and subsequently affects atmospheric circulation are then explored from the perspective of the hydrological effects of snow cover. Decreased (Increased) snow depth in Eurasia during the winter and spring directly leads to diminished (increased) soil moisture while increasing (decreasing) net radiation and sensible heat flux at the surface. The meridional distribution of surface temperature also exhibits a dipole pattern, leading to enhanced subtropical westerly jet in the upper troposphere. The Eurasian snow cover anomalies pattern triggered an anomalous mid-latitude Eurasian wave train, which strengthened significantly in the Western Siberian Plain. It then splits into two branches, one continuing to propagate eastward at high latitudes and the other shifting towards East Asia, thereby impacting precipitation in Eastern China. This work indicates that the second EOF mode of Eurasian snow cover can impact the precipitation variability in Eastern China during the same period and in summer on an interdecadal scale.

Rederiving kinetics to model biohydrogen production from immobilized microalgae alginate beads at various polymerization degrees of alginate under dark fermentative environment - Jia Min Woon; Kuan Shiong Khoo; Nurul Tasnim Sahrin; Fatima Musa Ardo; Jun Wei Lim; Woei-Yenn Tong; Yi Jing Chan; Chuxia Lin; Pei Sean Goh; Sabah Ansar; Man Kee Lam (Algal Research, 2024)

Children's food allergy: Effects of environmental influences and antibiotic use across critical developmental windows - Chan Lu; Ying Jiang; Mengju Lan; Lin Wang; Wanzhen Zhang; Faming Wang (Journal of Hazardous Materials, 2024)

A nationwide case-referent study on elevated risks of adenocarcinoma lung cancer by long-term PM2.5 exposure in Taiwan since 1997 - Wei-Chi Lin; Ruei-Hao Shie; Tzu-Hsuen Yuan; Chien-Hua Tseng; Chun-Ju Chiang; Wen-Chung Lee; Chang-Chuan Chan (Environmental Research, 2024)

The resistance to short-term dehydration in the bdelloid rotifer Rotaria rotatoria from different climate regions - Xianling Xiang; Chan Wang; Lin Huang; Lingyun Zhu; Jingyan Xu; Xinli Wen; Yilong Xi (Hydrobiologia, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

Detection of Turbulence Anomalies Using a Symbolic Classifier Algorithm in Airborne Quick Access Record (QAR) Data Analysis - Zibo Zhuang; Kunyun Lin; Hongying Zhang; Pak-Wai Chan (Advances in Atmospheric Sciences, 2024)

Estimates of the global burden of cancer-related deaths attributable to residential exposure to petrochemical industrial complexes from 2020 to 2040 - Hathaichon Boonhat; Yue Leon Guo; Chang-Chuan Chan; Ro-Ting Lin (Environmental Pollution, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Critical roles of tubular mitochondrial ATP synthase dysfunction in maleic acid-induced acute kidney injury - Hugo Y.-H. Lin; Chan-Jung Liang; Ming-Yu Yang; Phang-Lang Chen; Tzu-Ming Wang; Yen-Hua Chen; Yao-Hsiang Shih; Wangta Liu; Chien-Chih Chiu; Chih-Kang Chiang; Chang-Shen Lin; Han-Chen Lin (Apoptosis, 2024)
Maleic acid (MA) induces renal tubular cell dysfunction directed to acute kidney injury (AKI). AKI is an increasing global health burden due to its association with mortality and morbidity. However, targeted therapy for AKI is lacking. Previously, we determined mitochondrial-associated proteins are MA-induced AKI affinity proteins. We hypothesized that mitochondrial dysfunction in tubular epithelial cells plays a critical role in AKI. In vivo and in vitro systems have been used to test this hypothesis. For the in vivo model, C57BL/6 mice were intraperitoneally injected with 400 mg/kg body weight MA. For the in vitro model, HK-2 human proximal tubular epithelial cells were treated with 2 mM or 5 mM MA for 24 h. AKI can be induced by administration of MA. In the mice injected with MA, the levels of blood urea nitrogen (BUN) and creatinine in the sera were significantly increased ( p p p p p p

The Impact of Offshore Photovoltaic Utilization on Resources and Environment Using Spatial Information Technology - Peng Wang; Jingru Zhou; Xinfei Jin; Jingchao Shi; Ngai Weng Chan; Mou Leong Tan; Xingwen Lin; Xu Ma; Xia Lin; Kaixuan Zheng; Jiexuan Wu; Fei Zhang (Journal of Marine Science and Engineering, 2024)
In recent years, the rapid development of the photovoltaic (PV) industry has resulted in a saturation of research on onshore PV power plant construction. However, current studies on the impact of marine PVs on the marine environment remain limited and scarce. In order to facilitate the implementation of carbon reduction goals and promote the sustainable development of the offshore PV industry, this study analyzes the environmental impact of PV sea-use resources based on spatial information technology in the western part of Gaotang Island. The findings show that the MIKE21FM model provides relatively accurate simulations of tidal flow and tide level in the marine PV area. Flow velocity in the marine PV area exhibits a decreasing trend, with an average decrease ranging from 0.03 to 0.07 m/s. This decrease minimally affects surrounding navigational channels and large-scale flow fields. The resulting siltation is also deemed less significant, with an annual deposition from 0.03 to 0.06 m/a. Moreover, offshore PV construction resulted in a total intertidal biological loss of 123.45 t. The suspension of sediment during cofferdam construction and removal has a potential effect on zooplankton and fishery resources. Overall, it is proposed that careful planning, prudent site selection, and the execution of countermeasures during marine PV construction will combine to minimize the impact on the marine environment.

Microplastics in Asian rivers: Geographical distribution, most detected types, and inconsistency in methodologies - Hsin-Tien Lin; Falk Schneider; Muhamad Afiq Aziz; Keng Yinn Wong; Kantha D. Arunachalam; Sarva Mangala Praveena; Sumathi Sethupathi; Woon Chan Chong; Ayu Lana Nafisyah; Purushothaman Parthasarathy; Shreeshivadasan Chelliapan; Alexander Kunz (Environmental Pollution, 2024)

Impacts of physical parameterization scheme of snow and soil properties over the Tibetan Plateau on the simulation of summer rainfall in China - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Shiwen Wang; Yumeng Liu (Climate Dynamics, 2024)
Accurate representation of soil and snow state variables in the land surface model is crucial for good simulation results. In order to investigate the potential impacts of the overestimated snow cover over the Tibetan Plateau (TP) on precipitation over China, we designed comparative experiments over TP with and without updated soil texture data, soil hydrological parameters, and the fresh snow density scheme to address this issue with the Weather Research and Forecasting Model (WRF). The results show that snow cover fraction (SCF) and surface albedo in winter on the TP were overestimated in the WRF control experiment (CTL), with albedo bias exceeding 0.4 in the western TP. The SCF in the WRF improved experiment (WRFIM) is about 8% lower than that of the CTL, and the bias is decreased to 0.2–0.3 in the interior of the TP. The thermal and dynamic effects of the TP in winter have a significant impact on the weather and climate of East Asia during summer. Thus, the simulated summer rainfall bias is significantly reduced by WRFIM in North China, and the mid-lower reaches of the Yangtze River, along with the spatial correlation coefficient between the observed-based and WRF-simulated rainfall increased from 0.76 in CTL to 0.88 in WRFIM. The WRFIM-simulated reductions in snow cover and albedo cause a decrease in upward shortwave radiation and eventually increase net surface radiation. The horizontal temperature gradient of the atmosphere is increased in the WRFIM compared to the CTL, and the increased temperature in the lower and middle layers accommodates more water vapor, which is not conducive to precipitation formation. Correspondingly, the Western Pacific Subtropical High at 500 hPa in the middle troposphere weakened. The low-level anticyclonic circulation at 850 hPa also weakened to the east, affecting water vapor transport in eastern China. It leads to a decrease in the water vapor transported northward by southeasterly from the western Pacific Ocean and a decrease in the water vapor flux reaching North China. This work indicates that accurate characterization of soil properties and snow cover on the TP is crucial for improving the simulation bias of summer rainfall in China.

Pollution levels and ecological risks of PPCPs in water and sediment samples of Danjiangkou Reservoir - Haiyang Jin; Chan Yu; Li Lin; Jinghua Cheng; He Qin; Jingxiang Tao; Shengfei Deng (Environmental Science and Pollution Research, 2024)

Comparative analysis of Deinagkistrodon acutus venom from Taiwan and China utilizing chromatographic, electrophoretic, and bioinformatic approaches, along with ELISA employing a monospecific antivenom - Tein-Shun Tsai; Inn-Ho Tsai; Jing-Lin Qiu; Yuen-Ying Chan; Yu-Wei Chiang (Toxicon, 2024)

Interaction of life-time and early-life exposure to antibiotics and indoor environmental factors on childhood plant allergy - Chan Lu; Mengju Lan; Lin Wang; Ying Jiang; Bin Li; Faming Wang (Building and Environment, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Streptococcus taonis sp. nov., a novel bacterial species isolated from a blood culture of a patient - Chien-Yu Lee; Chin-Kan Chan; Momoko Chida; Mika Miyashita; Yun-Shien Lee; Hui-Chung Wu; Yu-Chung Chang; Wen-Ting Lin; Yi-Sheng Chen (Archives of Microbiology, 2024)

Population parameters and heterogeneity in survival rates of Indo-Pacific humpback dolphins in a heavily urbanized coastal region of southeast China: implications for conservation - Wenzhi Lin; Leszek Karczmarski; Stephen C. Y. Chan; Ruiqiang Zheng; Yuen-Wa Ho; Yaqian Mo (Frontiers in Marine Science, 2024)
The Pearl River Delta (PRD) region on the southeast coast of China is among the largest and most populated metropolitan regions of the world, subjecting the Indo-Pacific humpback dolphins ( Sousa chinensis ) inhabiting coastal waters of this region – apparently the largest population of this species – to intense anthropogenic pressure. In this 5-year study (2011-2015), we applied mark-recapture techniques to quantify population parameters of humpback dolphins in the main body of the extensive estuarine system of the Pearl River, the Lingding Bay (LB), the most urbanized and industrialized part of PRD. The super-population size was estimated at 928 individuals (95% CI=823-1046), which however over-represents the latest number of extant animals. Annual estimates fluctuated between 708 and 750 dolphins, and likely reflect most accurately the latest/current number of humpback dolphins in waters of LB. Both the overall and annual estimates generated by our study are considerably lower than previously published abundance estimates. Apparent survival rates were generally low, estimated at 0.943 (SE = 0.008, 95% CI = 0.929-0.958) and 0.815 (SE = 0.025, 95% CI = 0.766-0.866) for adults and juveniles, respectively. In conjunction with limited recruitment, they may have led to a substantial decline in population numbers over the past two decades. Notably, dolphins exhibited heterogeneous apparent survival rates across the complex anthropogenic seascape of LB. Adult individuals that use Hong Kong waters as their primary habitat exhibited 6.2% higher survival rates than those in other parts of LB. This difference tripled (19.2%) for juveniles, a likely expression of their susceptibility to environmental and/or anthropogenic stresses. We suggest that the difference in survival is largely due to heterogeneous anthropogenic stressors that vary spatially across the estuary, among which habitat loss, pollution, and declining prey resources appear to be the primary threats. Based on our latest findings, we call for a strategic conservation planning with the highest priority given to preserve the remaining key dolphin habitats in Hong Kong waters, and to quantify and mitigate the impacts of major stressor(s) in Guangdong (mainland China) waters. Given the encroachment of ever-more-intense human activities on the coastal habitats of humpback dolphins, understanding their demographic response and the underlying mechanisms of the population processes may prove instrumental in the formulation of a conservation management strategy that can secure their continuous survival.

TALE-based organellar genome editing and gene expression in plants - Jer-Young Lin; Yu-Chang Liu; Yan-Hao Tseng; Ming-Tsair Chan; Ching-Chun Chang (Plant Cell Reports, 2024)

High-Throughput SARS-CoV-2 Antiviral Testing Method Using the Celigo Image Cytometer - Laura A. St Clair; Leo Li-Ying Chan; Adam Boretsky; Bo Lin; Michael Spedding; Rushika Perera (Journal of Fluorescence, 2024)
The COVID-19 pandemic has created a worldwide public health crisis that has since resulted in 6.8 million reported deaths. The pandemic prompted the immediate response of researchers around the world to engage in rapid vaccine development, surveillance programs, and antiviral testing, which resulted in the delivery of multiple vaccines and repurposed antiviral drug candidates. However, the emergence of new highly transmissible SARS-CoV-2 variants has renewed the desire for discovering new antiviral drug candidates with high efficacy against the emerging variants of concern. Traditional antiviral testing methods employ the plaque-reduction neutralization tests (PRNTs), plaque assays, or RT-PCR analysis, but each assay can be tedious and time-consuming, requiring 2–3 days to complete the initial antiviral assay in biologically relevant cells, and then 3–4 days to visualize and count plaques in Vero cells, or to complete cell extractions and PCR analysis. In recent years, plate-based image cytometers have demonstrated high-throughput vaccine screening methods, which can be adopted for screening potential antiviral drug candidates. In this work, we developed a high-throughput antiviral testing method employing the Celigo Image Cytometer to investigate the efficacy of antiviral drug candidates on SARS-CoV-2 infectivity using a fluorescent reporter virus and their safety by measuring the cytotoxicity effects on the healthy host cell line using fluorescent viability stains. Compared to traditional methods, the assays defined here eliminated on average 3–4 days from our standard processing time for antiviral testing. Moreover, we were able to utilize human cell lines directly that are not typically amenable to PRNT or plaque assays. The Celigo Image Cytometer can provide an efficient and robust method to rapidly identify potential antiviral drugs to effectively combat the rapidly spreading SARS-CoV-2 virus and its variants during the pandemic.

Association between occupational noise and obesity: a retrospective cohort study in China - Geyang Li; Weile Wu; Li Zhou; Weiling Chan; Jin Wang; Lejia Zhu; Lin Song; Lan Lin; Beining Wu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2024)

Inherited BRCA1 and RNF43 pathogenic variants in a familial colorectal cancer type X family - James M. Chan; Mark Clendenning; Sharelle Joseland; Peter Georgeson; Khalid Mahmood; Jihoon E. Joo; Romy Walker; Julia Como; Susan Preston; Shuyi Marci Chai; Yen Lin Chu; Aaron L. Meyers; et al. (Familial Cancer, 2024)
Genetic susceptibility to familial colorectal cancer (CRC), including for individuals classified as Familial Colorectal Cancer Type X (FCCTX), remains poorly understood. We describe a multi-generation CRC-affected family segregating pathogenic variants in both BRCA1 , a gene associated with breast and ovarian cancer and RNF43 , a gene associated with Serrated Polyposis Syndrome (SPS). A single family out of 105 families meeting the criteria for FCCTX (Amsterdam I family history criteria with mismatch repair (MMR)-proficient CRCs) recruited to the Australasian Colorectal Cancer Family Registry (ACCFR; 1998–2008) that underwent whole exome sequencing (WES), was selected for further testing. CRC and polyp tissue from four carriers were molecularly characterized including a single CRC that underwent WES to determine tumor mutational signatures and loss of heterozygosity (LOH) events. Ten carriers of a germline pathogenic variant BRCA1 :c.2681_2682delAA p.Lys894ThrfsTer8 and eight carriers of a germline pathogenic variant RNF43 :c.988 C > T p.Arg330Ter were identified in this family. Seven members carried both variants, four of which developed CRC. A single carrier of the RNF43 variant met the 2019 World Health Organization (WHO 2019 ) criteria for SPS, developing a BRAF p.V600 wildtype CRC. Loss of the wildtype allele for both BRCA1 and RNF43 variants was observed in three CRC tumors while a LOH event across chromosome 17q encompassing both genes was observed in a CRC. Tumor mutational signature analysis identified the homologous recombination deficiency (HRD)-associated COSMIC signatures SBS3 and ID6 in a CRC for a carrier of both variants. Our findings show digenic inheritance of pathogenic variants in BRCA1 and RNF43 segregating with CRC in a FCCTX family. LOH and evidence of BRCA1-associated HRD supports the importance of both these tumor suppressor genes in CRC tumorigenesis.

Machine learning methods for the modelling and optimisation of biogas production from anaerobic digestion: a review - Jordan Yao Xing Ling; Yi Jing Chan; Jia Win Chen; Daniel Jia Sheng Chong; Angelina Lin Li Tan; Senthil Kumar Arumugasamy; Phei Li Lau (Environmental Science and Pollution Research, 2024)

Newcastle disease virus activates the PI3K/AKT signaling pathway by targeting PHLPP2 degradation to delay cell apoptosis and promote viral replication - Lei Fan; Zhaoping Liang; Jinlian Ren; Yichun Chen; He Zhu; Yanan Chen; Bin Xiang; Qiuyan Lin; Chan Ding; Libin Chen; Tao Ren (Veterinary Microbiology, 2024)

Preconceptional, pregnant, and postnatal exposure to outdoor air pollution and indoor environmental factors: Effects on childhood parasitic infections - Chan Lu; Lin Wang; Ying Jiang; Mengju Lan; Faming Wang (Science of The Total Environment, 2024)

A Multiplex Assay to Simultaneously Monitor Apoptosis and Necrosis Using the Cellaca® PLX Image Cytometer - Mackenzie Pierce; Yongyang Huang; Allen Lin; Carolina Franco Nitta; Dmitry Kuksin; Bo Lin; Leo Li-Ying Chan (Journal of Fluorescence, 2024)

Reciprocal transplant experiment reveals multiple factors influencing changes in coral microbial communities across climate zones - Ya-Fan Chan; Yu-Hsiang Chen; Sheng-Ping Yu; Hsing-Ju Chen; Yoko Nozawa; Sen-Lin Tang (Science of The Total Environment, 2024)

Polystyrene microplastics induce size-dependent multi-organ damage in mice: Insights into gut microbiota and fecal metabolites - Zhu Zhang; Wenqing Chen; Hiutung Chan; Junjie Peng; Peili Zhu; Junkui Li; Xiaoli Jiang; Zhang Zhang; Ying Wang; Zicong Tan; Yungkang Peng; Shiqing Zhang; et al. (Journal of Hazardous Materials, 2024)

Possibility of condensation of nitric acid for cloud condensation nucleus in the summer at Mt. Fuji - Kojiro Shimada; Yoshun Geka; Shungo Kato; Chak K. Chan; Yong Pyo Kim; Chang-Feng Ou-Yang; Neng-Huei Lin; Shiro Hatakeyama (Atmospheric Pollution Research, 2024)

A predictive model incorporating geomorphic factors for assessing the longevity of landslide-dammed lakes - Shao-Wei Wu; Wan-Yu Chan; Chao-Yuan Lin (Landslides, 2024)

Relationship between exposure to metalworking fluids and nonalcoholic fatty liver disease - Weiling Chan; Geyang Li; Li Zhou; Jin Wang; Lin Song; Lejia Zhu; Lan Lin; Beining Wu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2024)

Prediction and optimization of frying conditions of air fried pork rind using a direct linking model - Der-Sheng Chan; Hong-Ting Victor Lin; Yu-Hsiang Huang; Yu-Jin Syu; Wen-Chieh Sung (International Journal of Gastronomy and Food Science, 2023)

Cannabidiol protects the liver from α-Amanitin-induced apoptosis and oxidative stress through the regulation of Nrf2 - Haowei Wang; Genmeng Yang; Xiaoxing Zhang; Huijie Zhang; Yan Liu; Chan Wang; Lin Miao; Yi Li; Yizhen Huang; Hanxin Teng; Shangwen Wang; Hao Cheng; et al. (Food and Chemical Toxicology, 2023)

Environment-friendly organic coordination design of Z-scheme heterojunction N-BOB/BiOIO3 for efficient LED-light-driven photocatalytic and electrochemical performance - Yi-Lun Chen; Li Chen; Ming-Yen Sung; Jung-Hua Lin; Chao-Jan Liu; Chih-Jou Kuo; Er-Chieh Cho; Kuen-Chan Lee (Chemosphere, 2023)

Impacts of intrauterine and postnatal exposure to air pollution on preschool children's asthma: A key role in cumulative exposure - Chan Lu; Lin Wang; Hongsen Liao; Bin Li; Qin Liu; Qin Li; Faming Wang (Building and Environment, 2023)

New advance in biorenewable FDCA-based polyesters: Multiple scale-up from lab bench to pilot plant - Bo Wang; Zhu Tu; Xinyuan Zhang; Lin Sang; Wentao Chan; Lei Wang; Xinming Pu; Feng Ling; Min Qi; Zhiyong Wei (Chemical Engineering Journal, 2023)

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

Newcastle disease virus nucleocapsid protein mediates the degradation of 14–3–3ε to antagonize the interferon response and promote viral replication - Qiufan Xu; Jianpeng Liang; Jiaqi Jin; Wanyan Wu; Jinlian Ren; Jiayu Ruan; Lei Fan; Weifeng Yuan; Juncheng Cai; Qiuyan Lin; Bin Xiang; Chan Ding; et al. (Veterinary Microbiology, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

The role of meteorological parameters on childhood asthma: Identifying critical windows of susceptibility during pregnancy - Chan Lu; Hongsen Liao; Lin Wang; Qin Li; Qin Liu; Faming Wang (Building and Environment, 2023)

Trajectory Tracking Design for Unmanned Surface Vessels: Robust Control Approach - Yung-Hsiang Chen; Ming-Zhen Ellis-Tiew; Yu-Hsiang Chan; Guan-Wun Lin; Yung-Yue Chen (Journal of Marine Science and Engineering, 2023)
We propose a robust nonlinear trajectory tracking design by integrating a nonlinear model transformation, robust disturbance eliminator, and trajectory generator for unmanned surface vessels influenced by modeling uncertainties and ocean environmental disturbances. We designed this nonlinear control law to help control unmanned surface vessels following any designated sail trajectory constructed by the trajectory generator. With cubic spline interpolation, this trajectory generator can generate arbitrary smooth trajectories. Simulation results show that the proposed nonlinear robust control law has precise trajectory tracking performance and a robustness property for unmanned surface vessels under harsh ocean environmental disturbances and modeling uncertainties.

mRNA sequencing and CyTOF analysis revealed ASPP2 altered the response patterns of hepatocellular carcinoma HepG2 cells to usnic acid - Yang Wang; Yadong Yan; Yunfei Huo; Yuheng Pang; Liujia Chan; Shanshan Wang; Dexi Chen; Dongdong Lin; Wenjing Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Correction: Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2023)

α-amanitin induces autophagy through AMPK-mTOR-ULK1 signaling pathway in hepatocytes - Yue Xu; Shangwen Wang; Chi-Kwan Leung; Hao Chen; Chan Wang; Huijie Zhang; Shuwei Zhang; Yi Tan; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Toxicology Letters, 2023)

Feasibility of a TDR-based technique for fluid hydrocarbon leak detection - Chih-Ping Lin; Yin Jeh Ngui; Yi-Pei Chan; Albert T. Yeung (Process Safety and Environmental Protection, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Physiological response of red macroalgae Pyropia yezoensis (Bangiales, Rhodophyta) to light quality: a short-term adaptation - Xuefeng Zhong; Shuai Che; Congying Xie; Lan Wu; Xinyu Zhang; Lin Tian; Chan Liu; Hongbo Li; Guoying Du (Algae, 2023)
Light quality is a common environmental factor which influences the metabolism of biochemical substances in algae and leads to the response of algal growth and development. Pyropia yezoensis is a kind of economic macroalgae that naturally grows in the intertidal zone where the light environment changes dramatically. In the present study, P. yezoensis thalli were treated under white light (control) and monochromatic lights with primary colors (blue, green, and red) for 14 days to explore their physiological response to light quality. During the first 3 days of treatment, P. yezoensis grew faster under blue light than other light qualities. In the next 11 days, it showed better adaptation to green light, with higher growth rate and photosynthetic capacity (reflected by a higher rETRmax = 61.58 and Ek = 237.78). A higher non-photochemical quenching was observed in the treatment of red light than others for 14 days. Furthermore, the response of P. yezoensis to light quality also results in the difference of photosynthetic pigment contents. The monochromatic light could reduce the synthesis of all pigments, but the reduction degree was different, which may relate to the spectral absorption characteristics of pigments. It was speculated that P. yezoensis adapted to a specific or changing light environments by regulating the synthesis of pigments to achieve the best use of light energy in photosynthesis and premium growth and metabolism.

Newcastle disease virus activates methylation-related enzymes to reprogram m6A methylation in infected cells - Weifeng Yuan; Yuechi Hou; Qingyi Wang; Ting Lv; Jinlian Ren; Lei Fan; Juncheng Cai; Bin Xiang; Qiuyan Lin; Ming Liao; Chan Ding; Libin Chen; et al. (Veterinary Microbiology, 2023)

Water-soluble propolis extract as a natural preservative for jaboticaba juice - Lee Suan Chua; Yi Lin Chan; Zhi Ying Tay; John Soo (Food Bioscience, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

HAI-1 is required for the novel role of FGFBP1 in maintenance of cell morphology and F-actin rearrangement in human keratinocytes - Dajun D. Lu; Nanxi Huang; Sheng-Wen A. Li; Jessica R. Fang; Chih-Hsin Lai; Jehng-Kang Wang; Khee-Siang Chan; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2023)

Transition of carbon-nitrogen coupling under different anthropogenic disturbances in subtropical small mountainous rivers - Li-Chin Lee; Gabriele Weigelhofer; Thomas Hein; Shin-Chien Chan; Ying-San Liou; Chien-Sen Liao; Fuh-Kwo Shiah; Yu-Lin Yu; Tsung-Yu Lee; Jr-Chuan Huang (Science of The Total Environment, 2023)

Unveiling the effect of structural water on Zn-ion storage of polyoxovanadate for high-rate and long-life aqueous zinc ion battery - Huan He; Fu-Chun Pan; Xue-Wei Liang; Qiang Hu; Shude Liu; Jisong Hu; Seong Chan Jun; Dunmin Lin; Yusuke Yamauchi; Yu Huo (Chemical Engineering Journal, 2023)

The impact of temperature and precipitation on all-infectious-, bacterial-, and viral-diarrheal disease in Taiwan - Gerry Andhikaputra; Amir Sapkota; Yu-Kai Lin; Ta-Chien Chan; Chuansi Gao; Li-Wen Deng; Yu-Chun Wang (Science of The Total Environment, 2023)

Chromatin modifiers: A new class of pollutants with potential epigenetic effects revealed by in vitro assays and transcriptomic analyses - Chi Tim Leung; Yi Yang; Ting Fung Chan; Xiao Lin; Alice Sze Tsai Wong; Wing Yee Lui; Karen Wing Yee Yuen; Richard Yuen Chong Kong; Keng Po Lai; Rudolf Shiu Sun Wu (Toxicology, 2023)

Functionalized photosensitive metal-organic framework as a theranostic nanoplatform for turn-on detection of MicroRNA and photodynamic therapy - Chan Yang; Kun Wang; Shuo Tian; Liuting Mo; Weiying Lin (Analytica Chimica Acta, 2023)

A novel antibacterial tyroscherin derivative with a natural unprecedented morpholine-2, 3-dione structural unit from the fungus Pseudallescheria boydii - Ruolan Chen; Ziyang Li; Chan Qin; Peijun Lu; Jiaru Lin; Wenxu Zheng; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

Spatial–temporal variations and pollution risks of mercury in water and sediments of urban lakes in Guangzhou City, South China - Xiaojun Wang; Wei Zhong; Bingxiang Wang; Mingying Quan; Tianhang Li; Durui Lin; Shengtan Shang; Chan Zhu; Churan Zhang; Yiling Liao (Environmental Science and Pollution Research, 2022)

Evaluation of the Potential of the Hard Clam (Meretrix meretrix) Shell Which Can Be Used as the Bioindicator for Heavy Metal Accumulation - Yen-Ting Lin; Fang-Chi Chang; Ming-Tsung Chung; Ze-Kai Li; Chang-Chuan Chan; Ying-Sheng Huang; Kuo-Fang Huang; Yu-San Han (Fishes, 2022)
Clams, Meretrix meretrix, were one of the favorite aquatic products in Taiwan and the world. It was reported that the water pollutants such as heavy metals and chemicals might accumulate in the clam body and shell through filter-feeding behavior. Thus, the bivalves could be used as bioindicators in the aquatic environment. The present study analyzed 20 trace elements, Mg, Sr, Li, Cd, Ba, Mn, Al, U, Ti, Pb, Nd, B, S, Zn, Fe, P, Na, K, Cu, and Ni, in the shells of the clams collected from the wild coastal area and cultured ponds to evaluate which elements have the potential to be biomarkers. The concentrations of 20 elements were detected by Solution-Based Inductively Coupled Plasma Mass Spectrometry (SB-ICPMS). Among them, Cd, Al, U, Ti, Nd, S, and K were below the detection limit. The remaining elements were analyzed for accumulation. The levels of Zn, Fe, and Ni possess high variation in an identical environment; so, a PCA was conducted without these three elements to reduce noise. The PCA result proved that the clam could absorb specific trace elements from the habitat. After a period of time, the contents of the absorption in the shells of the clams living in an identical environment became more similar. The analyzed element, Pb, was not found with a special difference in this study. The levels of Na, Sr, Mg, B, Mn, P, Ba, Li, and Cu reflected different sampling sites, which suggested that these elements in the species M. meretrix had the potential to be used as biomarkers for assessing heavy metal accumulation in the environment.

Theranostic Radiolabeled Nanomaterials for Molecular Imaging and potential Immunomodulation Effects - Chao-Cheng Chen; Yang-Hsiang Chan; Syue-Liang Lin; Huihua Kenny Chiang; Yi-Jang Lee; Hui-Yen Chuang (Journal of Medical and Biological Engineering, 2022)

The role of MeCP2 and the BDNF/TrkB signaling pathway in the stress resilience of mice subjected to CSDS - Lixuan Huang; Lujuan He; Ruijia Ma; Wanzhao Ding; Chan Zhou; Song Lin; Ji-chun Zhang; Jiaxu Chen; Wei Yao (Psychopharmacology, 2022)

An unknown component of a well-known population: socio-demographic parameters of Indo-Pacific humpback dolphins (Sousa chinensis) at the western reaches of the Pearl River Delta region - Stephen C. Y. Chan; Leszek Karczmarski; Wenzhi Lin; Ruiqiang Zheng; Yuen-Wa Ho; Lang Guo; Yaqian Mo; Andy T. L. Lee; Carmen K. M. Or; Yuping Wu (Mammalian Biology, 2022)

Biflavonoids from the twigs and leaves of Cephalotaxus oliveri Mast. and their α -glucosidase inhibitory activity - Min Song; Tong Xiao; Qiu-Shuang Wu; Hang Fai Kwok; Ging Chan; Li-Gen Lin; Xiao-Qi Zhang; Wen-Cai Ye; Sheng-Jiang He; Qing-Wen Zhang (Natural Product Research, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

In Vitro Assessment of Transporter Mediated Perpetrator DDIs for Several Hepatitis C Virus Direct-Acting Antiviral Drugs and Prediction of DDIs with Statins Using Static Models - Xiaoyan Chu; Grace Hoyee Chan; Robert Houle; Meihong Lin; Jocelyn Yabut; Christine Fandozzi (The AAPS Journal, 2022)

Political ideology and psychological reactance: how serious should climate change be? - Eugene Y. Chan; Jack Lin (Climatic Change, 2022)

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Common Subtype of Small Renal Mass MR Imaging Characterisation: A Medical Center Experience in Taiwan - Ming-Cheng Liu; Yi-Jui Liu; Yen-Ting Lin; Siu-Wan Hung; Jyh-Wen Chai; Si-Wa Chan; Kun-Yuan Chiu; Ya-Ling Tsou (Journal of Medical and Biological Engineering, 2022)
Purpose Many studies have shown that multiparametric magnetic resonance imaging (MRI) may be helpful for differentiating malignant renal cell carcinomas (RCCs) from benign lesions. However, the key imaging characteristics that differ between malignant and benign tumors still require further discussion. Methods We analyzed 60 adult patients diagnosed with 72 small renal masses (SRMs) who received preoperative MRI from 2014 to 2019 at a hospital in Taiwan. The MRI features included conventional MRI parameters, diffusion-weighted imaging (DWI) data, and dynamic contrast-enhanced (DCE) patterns, which were documented and compared among the four common subtypes: clear cell RCC (ccRCC), papillary RCC (pRCC), angiomyolipoma (AML) and other types of RCC. The apparent diffusion coefficient (ADC) values of high- and low-grade RCCs were also analyzed. Results The results show that ccRCC had higher T2-weighted signal intensity than the other three subgroups, a higher arterial wash-in index (AWI) and ADC value than AML and pRCC, and manifested a plateau ( n = 9, 25%) or washout (n = 27, 75%) enhancement pattern. AMLs exhibited more intravoxel fat than the other three subtype groups, and half of the AMLs (6 in 12) contained bulk fat. pRCC demonstrated a more progressive (n = 3, 60%) enhancement pattern than the other three subgroups. The ADC value of high-grade RCCs was significantly lower than that of low-grade RCCs. Conclusion These findings may indicate that multiparametric MRI is useful in differentiating among four common pathological types of SRMs, and the ADC value may be helpful in evaluating the histological grade of malignancy.

miRNA–mRNA Integrative Analysis Reveals the Roles of miRNAs in Hypoxia-Altered Embryonic Development- and Sex Determination-Related Genes of Medaka Fish - Keng Po Lai; Nathan Yi Kan Tam; Yuelong Chen; Chi Tim Leung; Xiao Lin; Chau Fong Tsang; Yin Cheung Kwok; William Ka Fai Tse; Shuk Han Cheng; Ting Fung Chan; Richard Yuen Chong Kong (Frontiers in Marine Science, 2022)
Recent studies have shown hypoxia to be an endocrine disruptor that impairs sex differentiation and reproductive function, leading to male-biased F1 populations in fish. However, the molecular mechanisms through which hypoxia alters fish sex differentiation and therefore sex ratios remain poorly understood. In order to understand the potential role of miRNAs in mediating hypoxia-altered sex determination and differentiation in fish, we conducted small RNA sequencing and transcriptome sequencing on marine medaka ( Oryzias melastigma ) embryos that were exposed to hypoxia (2.0 ± 0.2 mg O 2 L – 1) for 40 h (encompassing a critical window of sex determination). We identified dysregulated miRNAs and mRNAs in the hypoxia-exposed embryo, and bioinformatic analysis of the integrative small RNA sequencing and transcriptome sequencing results revealed hypoxia to cause alterations of genes related to embryonic development through miRNA regulation. Importantly, we have identified miRNA-mRNA pairs that were reported to play roles in gonad development (novel miR-145-col9a3 and novel miRNA-94- arid5b), in sex hormone response (novel miRNA-210-ca2, novel miRNA-106-nr2f2, nbr-miR-29c-nr4a1, and ola-miR-92b-akr1d1), and in sex characteristic development (novel miRNA-145-mns1, nle-miR-20-sord, and ipu-miR-219b-abcc8). Our findings highlighted the possible roles of miRNA–mRNA in regulation of embryonic development and sex determination in response to hypoxic stress.

Dosimetric evaluation of a patient-specific 3D-printed oral positioning stent for head-and-neck radiotherapy - Susannah Cleland; Philip Chan; Benjamin Chua; Scott B. Crowe; Jodi Dawes; Lizbeth Kenny; Charles Lin; Elise Obereigner; Samuel C. Peet; Jamie V. Trapp; Tania Poroa; Tanya Kairn (Physical and Engineering Sciences in Medicine, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Distributions of Total Mercury and Methylmercury in Dragonflies from a Large, Abandoned Mercury Mining Region in China - Gaoen Wu; Shunlin Tang; Jialiang Han; Chan Li; Lin Liu; Xiaohang Xu; Zhidong Xu; Zhuo Chen; Yajie Wang; Guangle Qiu (Archives of Environmental Contamination and Toxicology, 2021)

Proteomic Response of the Brain to Hypoxic Stress in Marine Medaka Fish (Oryzias melastigma) - Keng Po Lai; Nathan Tam; Simon Yuan Wang; William Ka Fai Tse; Xiao Lin; Ting Fung Chan; Yin Tong; Jianwen Zhang; Doris Wai Ting Au; Rudolf Shiu Sun Wu; Richard Yuen Chong Kong (Frontiers in Marine Science, 2021)
Hypoxia is a serious issue that affects the marine environment, with a growing number of hypoxic “dead zones” occurring each year. Reports have indicated that hypoxia is detrimental to the reproductive function and sexual development of fish via the disruption of endocrine signaling in organs involved in the hypothalamus–pituitary–gonad axis, including the brain. While we previously reported that hypoxia induces transcriptome-wide alterations in the brain of marine medaka ( Oryzias melastigma ), whether these effects were reflected at the protein level remains unclear. Therefore, the present study used high-throughput proteomic sequencing along with bioinformatics analysis to assess the short-term and multi-generational effects of hypoxia on the brain proteome of O. melastigma . We identified 36,567 peptides and 7,599 proteins (1% false discovery rate in brain samples), with functions involved in cellular and metabolic processes such as signaling and reproductive processes as well as energy production and conversion. Furthermore, we determined that hypoxia resulted in the significant differential expressions of 33 upregulated and 69 downregulated proteins in the short-term exposure group and 24 upregulated and 52 downregulated proteins in the multi-generational exposure group. Pathway enrichment analysis of the deregulated proteins indicated that hypoxia could impair brain function by altering arachidonic acid metabolism, tight junctions, and adrenergic signaling under short-term hypoxic exposure and by altering p53 and PI3K–Akt signaling under multi-generational hypoxic exposure, which may lead to the onset of neurodegenerative disorders including Alzheimer’s disease and amyotrophic lateral sclerosis. Ingenuity pathway analysis of the deregulated proteins showed that hypoxia affected common signaling pathways in the brain (e.g., integrin, paxillin, and epithelial adherens junction signaling) under both short-term and multi-generational exposures. Hypoxia also deregulated pathways specific to short-term exposure (including integrin-linked kinase, calcium, and integrin signaling) and multi-generational exposure (including sphingosine-1-phosphate signaling, endocannabinoid neuronal synapse pathway, and endoplasmic reticulum stress pathway). Overall, our results provide additional insights into the mechanisms of hypoxia disrupting neuronal function at the protein level in marine medaka.

Genetic architecture of wild soybean (Glycine soja Sieb. and Zucc.) populations originating from different East Asian regions - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Hon-Ming Lam; Faheem Shehzad Baloch; Muhammad Amjad Ali; Kirill S. Golokhvast; Seung Hwan Yang; Gyuhwa Chung (Genetic Resources and Crop Evolution, 2021)

Microbiome Reengineering by Heat Selection for Rapid Biodegradation of Trichloroethylene with Minimal Vinyl Chloride Formation - Ai-Lin Chan; Chien-Yun Tseng; Tzu-Wen Chen; Yi-Hsuan Lo; Shu-Chi Chang (Water, Air, & Soil Pollution, 2021)

A Comprehensive Assessment of All-Oleate Polysorbate 80: Free Fatty Acid Particle Formation, Interfacial Protection and Oxidative Degradation - Nidhi Doshi; Jamie Giddings; Lin Luis; Arthur Wu; Kyle Ritchie; Wenqiang Liu; Wayman Chan; Rosalynn Taing; Jeff Chu; Alavattam Sreedhara; Aadithya Kannan; Pervina Kei; et al. (Pharmaceutical Research, 2021)

Machine learning prediction of neurocognitive impairment among people with HIV using clinical and multimodal magnetic resonance imaging data - Yunan Xu; Yizi Lin; Ryan P. Bell; Sheri L. Towe; John M. Pearson; Tauseef Nadeem; Cliburn Chan; Christina S. Meade (Journal of NeuroVirology, 2021)

Identification through fine mapping and verification using CRISPR/Cas9-targeted mutagenesis for a minor QTL controlling grain weight in rice - Aye Nyein Chan; Lin-Lin Wang; Yu-Jun Zhu; Ye-Yang Fan; Jie-Yun Zhuang; Zhen-Hua Zhang (Theoretical and Applied Genetics, 2021)
Key message A minor QTL for grain weight in rice, qTGW1.2b , was fine-mapped. Its casual gene OsVQ4 was confirmed through CRISPR/Cas9-targeted mutagenesis, exhibiting an effect that was larger than the original QTL effect. Abstract The CRISPR/Cas system exhibits a great potential for rice improvement, but the application was severely hindered due to insufficient target genes, especial the lack of validated genes underlying quantitative trait loci having small effects. In this study, a minor QTL for grain weight, qTGW1.2b , was fine-mapped into a 44.0 kb region using seven sets of near isogenic lines (NILs) developed from the indica rice cross (Zhenshan 97) 3 /Milyang 46, followed by validation of the causal gene using CRISPR/Cas9-targeted mutagenesis. In the NIL populations, 1000-grain weight of the Zhenshan 97 homozygous lines decreased by 0.9–2.0% compared with the Milyang 46 homozygous lines. A gene encoding VQ-motif protein, OsVQ4 , was identified as the candidate gene based on parental sequence differences. The effect of OsVQ4 was confirmed by creating CRISPR/Cas9 knockout lines, whose 1000-grain weight decreased by 2.8–9.8% compared with the wild-type transgenic line and the recipient. These results indicate that applying genome editing system could create novel alleles with large phenotypic variation at minor QTLs, which is an effective way to validate causal genes of minor QTLs. Our study establishes a strategy for cloning minor QTLs, which could also be used to identify a large number of potential target genes for the application of CRISPR/Cas system.

Low ambient temperature increases hospital re-admissions for systemic lupus erythematosus in humid subtropical region: a time series study - Qian Wu; Zhiwei Xu; Yi-Lin Dan; Peng Wang; Yan-Mei Mao; Chan-Na Zhao; Yan-Feng Zou; Dong-Qing Ye; Wenbiao Hu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

PBPK modeling of CYP3A and P-gp substrates to predict drug–drug interactions in patients undergoing Roux-en-Y gastric bypass surgery - Kuan-Fu Chen; Lingtak-Neander Chan; Yvonne S. Lin (Journal of Pharmacokinetics and Pharmacodynamics, 2020)

Embryonic gene expression altered by maternal exposure to air pollution in rats - Zheng Li; Jianqing Ma; Youxi Lin; Jianxiong Shen; Zhanyong Wu; Matthew T. V. Chan; William K. K. Wu (Environmental Science and Pollution Research, 2020)

Immune effect of a Newcastle disease virus DNA vaccine with IL-12 as a molecular adjuvant delivered by electroporation - Peng Xie; Yanling Li; Yaling Li; Jianpeng Liang; Bin Xiang; Qiuyan Lin; Jiaqi Jin; Chan Ding; Chenggang Xu; Tao Ren (Archives of Virology, 2020)

Osmotic stress induces gut microbiota community shift in fish - Keng Po Lai; Xiao Lin; Nathan Tam; Jeff Cheuk Hin Ho; Marty Kwok‐Shing Wong; Jie Gu; Ting Fung Chan; William Ka Fai Tse (Environmental Microbiology, 2020)
Summary Alteration of the gut microbiota plays an important role in animal health and metabolic diseases. However, little is known with respect to the influence of environmental osmolality on the gut microbial community. The aim of the current study was to determine whether the reduction in salinity affects the gut microbiota and identify its potential role in salinity acclimation. Using Oryzias melastigma as a model organism to perform progressive hypotonic transfer experiments, we evaluated three conditions: seawater control (SW), SW to 50% sea water transfer (SFW) and SW to SFW to freshwater transfer (FW). Our results showed that the SFW and FW transfer groups contained higher operational taxonomic unit microbiota diversities. The dominant bacteria in all conditions constituted the phylum Proteobacteria , with the majority in the SW and SFW transfer gut comprising Vibrio at the genus level, whereas this population was replaced by Pseudomonas in the FW transfer gut. Furthermore, our data revealed that the FW transfer gut microbiota exhibited a reduced renin–angiotensin system, which is important in SW acclimation. In addition, induced detoxification and immune mechanisms were found in the FW transfer gut microbiota. The shift of the bacteria community in different osmolality environments indicated possible roles of bacteria in facilitating host acclimation.

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

An alternative splicing variant of mineralocorticoid receptor discovered in preeclampsia tissues and its effect on endothelial dysfunction - Mengxi Guo; Chengliang Zhou; Gufeng Xu; Lin Tang; Yechun Ruan; Ying Yu; Xianhua Lin; Dandan Wu; Hao Chen; Priscilla Yu; Luyang Jin; Yinyu Wang; et al. (Science China Life Sciences, 2020)

Optic lobe organization in stomatopod crustacean species possessing different degrees of retinal complexity - Chan Lin; Alice Chou; Thomas W. Cronin (Journal of Comparative Physiology A, 2020)

The potential of satellite remote sensing for monitoring the onset of volcanic activity on Taipei’s doorstep - Hai-Po Chan; Chung-Pai Chang; Tang-Huang Lin; Matthew Blackett; Hao Kuo-Chen; Andrew Tien-Shun Lin (International Journal of Remote Sensing, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

A New Neural Pathway from the Ventral Striatum to the Nucleus Basalis of Meynert with Functional Implication to Learning and Memory - Si Yun Shu; Gang Jiang; Zhaocong Zheng; Lin Ma; Bin Wang; Qiyi Zeng; Hong Li; Shen Tan; Bin Liu; Wood Yee Chan; Sheng Wu; Chunhua Zhu; et al. (Molecular Neurobiology, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Antagonism of Ca2+-sensing receptors by NPS 2143 is transiently masked by p38 activation in mouse brain bEND.3 endothelial cells - Cing-Yu Chen; Mann-Jen Hour; Wen-Chuan Lin; Kar-Lok Wong; Lian-Ru Shiao; Ka-Shun Cheng; Paul Chan; Yuk-Man Leung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Characterization of Cellulose Synthase A (CESA) Gene Family in Eudicots - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Muhammad Imtiaz; Hafiz Mamoon Rehman; Muhammad Amjad Ali; Faheem Shehzad Baloch; Rana Muhammad Atif; Seung Hwan Yang; Gyuhwa Chung (Biochemical Genetics, 2019)

Oral Administration of Compound Probiotics Ameliorates HFD-Induced Gut Microbe Dysbiosis and Chronic Metabolic Inflammation via the G Protein-Coupled Receptor 43 in Non-alcoholic Fatty Liver Disease Rats - Yinji Liang; Shu Liang; Yupei Zhang; Yuanjun Deng; Yifang He; Yanning Chen; Chan Liu; Chenli Lin; Qinhe Yang (Probiotics and Antimicrobial Proteins, 2019)

Neonatal Dexamethasone Treatment Suppresses Hippocampal Estrogen Receptor α Expression in Adolescent Female Rats - Hui-Fang Chiu; Michael W. Y. Chan; Chiung-Yin Cheng; Jian-Liang Chou; Jora Meng-Ju Lin; Yi-Ling Yang; Kwok-Tung Lu (Molecular Neurobiology, 2019)

A differential k-mer analysis pipeline for comparing RNA-Seq transcriptome and meta-transcriptome datasets without a reference - Chon-Kit Kenneth Chan; Nedeljka Rosic; Michał T. Lorenc; Paul Visendi; Meng Lin; Paulina Kaniewska; Brett J. Ferguson; Peter M. Gresshoff; Jacqueline Batley; David Edwards (Functional & Integrative Genomics, 2019)

Understanding the Impacts of Surface Compositions on the In-Vitro Dissolution and Aerosolization of Co-Spray-Dried Composite Powder Formulations for Inhalation - Sharad Mangal; Rongkun Xu; Heejun Park; Dmitry Zemlyanov; Nivedita Shetty; Yu-Wei Lin; David Morton; Hak-Kim Chan; Jian Li; Qi Tony Zhou (Pharmaceutical Research, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Heavy Metal Components in Blood and Urinary Stones of Urolithiasis Patients - Yunhe Yen; Borshuh Cheng; Changchung Chan; Chiwei Lin; Hsiuling Chen (Biological Trace Element Research, 2018)

A large meta-analysis of the global prevalence rates of S. aureus and MRSA contamination of milk - Qianting Ou; Junli Zhou; Dongxin Lin; Chan Bai; Ting Zhang; Jialing Lin; Haoqu Zheng; Xiaojie Wang; Jiaping Ye; Xiaohua Ye; Zhenjiang Yao (Critical Reviews in Food Science and Nutrition, 2018)

Probiotic mixture of Lactobacillus and Bifidobacterium alleviates systemic adiposity and inflammation in non-alcoholic fatty liver disease rats through Gpr109a and the commensal metabolite butyrate - Yinji Liang; Chenli Lin; Yupei Zhang; Yuanjun Deng; Chan Liu; Qinhe Yang (Inflammopharmacology, 2018)

Transcriptional responses of the marine green alga Micromonas pusilla and an infecting prasinovirus under different phosphate conditions - Charles Bachy; Christina J. Charlesworth; Amy M. Chan; Jan F. Finke; Chee‐Hong Wong; Chia‐Lin Wei; Sebastian Sudek; Maureen L. Coleman; Curtis A. Suttle; Alexandra Z. Worden (Environmental Microbiology, 2018)
Summary Prasinophytes are widespread marine algae for which responses to nutrient limitation and viral infection are not well understood. We studied the picoprasinophyte, Micromonas pusilla , grown under phosphate‐replete (0.65 ± 0.07 d −1 ) and 10‐fold lower (low)‐phosphate (0.11 ± 0.04 d −1 ) conditions, and infected by the phycodnavirus MpV‐SP1. Expression of 17% of Micromonas genes in uninfected cells differed by >1.5‐fold ( q

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Diversity of microbiota associated with symptomatic and non-symptomatic bacterial wilt-diseased banana plants determined using 16S rRNA metagenome sequencing - Nurul Shamsinah Mohd Suhaimi; Share-Yuan Goh; Noni Ajam; Rofina Yasmin Othman; Kok-Gan Chan; Kwai Lin Thong (World Journal of Microbiology and Biotechnology, 2017)

Risk factors and outcome of levofloxacin-resistant Elizabethkingia meningoseptica bacteraemia in adult patients in Taiwan - Y.-C. Huang; Y.-W. Huang; Y.-T. Lin; F.-D. Wang; Y.-J. Chan; T.-C. Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Different responses of influenza epidemic to weather factors among Shanghai, Hong Kong, and British Columbia - Xi-Ling Wang; Lin Yang; Dai-Hai He; Alice PY Chiu; Kwok-Hung Chan; King-Pan Chan; Maigeng Zhou; Chit-Ming Wong; Qing Guo; Wenbiao Hu (International Journal of Biometeorology, 2017)

Prior Visual Experience Modulates Learning of Sound Localization Among Blind Individuals - Qian Tao; Chetwyn C. H. Chan; Yue-jia Luo; Jian-jun Li; Kin-hung Ting; Zhong-lin Lu; Susan Whitfield-Gabrieli; Jun Wang; Tatia M. C. Lee (Brain Topography, 2017)

Distribution of a Coastal Delphinid Under the Impact of Long-Term Habitat Loss: Indo-Pacific Humpback Dolphins off Taiwan’s West Coast - Leszek Karczmarski; Shiang-Lin Huang; Wai-Ho Wong; Wei-Lun Chang; Stephen C.Y. Chan; Mark Keith (Estuaries and Coasts, 2017)

Characterization of nanocellulose recovery from Elaeis guineensis frond for sustainable development - Muhammad Safwan Mohaiyiddin; Ong Hui Lin; Wei Tieng Owi; Chi Hoong Chan; Chin Hua Chia; Sarani Zakaria; Al Rey Villagracia; Hazizan Md Akil (Clean Technologies and Environmental Policy, 2016)

The summer distribution of coccolithophores and its relationship to water masses in the East China Sea - Lee-Kuo Kang; Hsing-Ming Lu; Pei-Ting Sung; Ya-Fan Chan; Yun-Chi Lin; Gwo-Ching Gong; Kuo-Ping Chiang (Journal of Oceanography, 2016)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

Efficacy and safety of interferon-α2b spray in the treatment of hand, foot, and mouth disease: a multicenter, randomized, double-blind trial - Hailong Lin; Leting Huang; Jian Zhou; Kaichun Lin; Hongjiao Wang; Xia Xue; Chan Xia (Archives of Virology, 2016)

Catastrophic outburst and tsunami flooding of Lake Baikal: U–Pb detrital zircon provenance study of the Palaeo-Manzurka megaflood sediments - Alexei V. Ivanov; Elena I. Demonterova; Leonid Z. Reznitskii; Igor G. Barash; Sergey G. Arzhannikov; Anastasia V. Arzhannikova; Chan-Hui Hung; Sun-Lin Chung; Yoshiyuki Iizuka (International Geology Review, 2016)

The modulation of Th2 immune pathway in the immunosuppressive effect of human umbilical cord mesenchymal stem cells in a murine asthmatic model - Chin-Kan Chan; Ting-Chun Lin; Yung-An Huang; Ya-Shan Chen; Chia-Ling Wu; Huei-Yu Lo; Ming-Ling Kuo; Kang-Hsi Wu; Jing-Long Huang (Inflammation Research, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Betaine enhances antidepressant-like, but blocks psychotomimetic effects of ketamine in mice - Jen-Cheng Lin; Mei-Yi Lee; Ming-Huan Chan; Yi-Chyan Chen; Hwei-Hsien Chen (Psychopharmacology, 2016)

Infanticide in the Indo-Pacific humpback dolphin (Sousa chinensis) - Ruiqiang Zheng; Leszek Karczmarski; Wenzhi Lin; Stephen C. Y. Chan; Wei-Lun Chang; Yuping Wu (Journal of Ethology, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Three duplication events and variable molecular evolution characteristics involved in multiple GGPS genes of six Solanaceae species - FENG LI; CHUNYANG WEI; CHAN QIAO; ZHENXI CHEN; PENG WANG; PAN WEI; RAN WANG; LIFENG JIN; JUN YANG; FUCHENG LIN; ZHAOPENG LUO (Journal of Genetics, 2016)

Spatio-temporal distribution of flood disasters and analysis of influencing factors in Africa - Chan-juan Li; Yuan-qing Chai; Lin-sheng Yang; Hai-rong Li (Natural Hazards, 2016)

Strong inhibition of betanodavirus replication by ribavirin targeting RNA ‐dependent RNA polymerase - Y‐C Huang; T‐S Lin; C Peng; N‐L Chan; Y‐S Han (Journal of Fish Diseases, 2016)

Resistance to viral yellow leaf curl in tomato through RNAi targeting two Begomovirus species strains - Huei-mei Chen; Chen-yu Lin; Wen-shi Tsai; Lawrence Kenyon; Ming-tsair Chan; Jo-yi Yen; Shao-yu Chang; Robert de la Peña; Roland Schafleitner (Journal of Plant Biochemistry and Biotechnology, 2016)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

In Vivo Sodium MRI for Mouse Model of Ischemic Stroke at 7 T: Preliminary Results - Kun-Che Lee; Jen-Fang Yu; Yi-Shin Lee; Guo-Jen Huang; Hsiao-Lung Chan; In-Tsang Lin; Jyh-Honrg Chen (Journal of Medical and Biological Engineering, 2015)

A biodegradable ocular implant for long-term suppression of intraocular pressure - Xu Wen Ng; Kerh Lin Liu; Amutha Barathi Veluchamy; Nyein Chan Lwin; Tina T. Wong; Subbu S. Venkatraman (Drug Delivery and Translational Research, 2015)

Neurology of the H1N1 pandemic in Singapore: a nationwide case series of children and adults - Asha Prerna; Jocelyn Y. X. Lim; Natalie W. H. Tan; Mas Suhaila Isa; Helen May-Lin Oh; Norazieda Yassin; Chian-Yong Low; Derrick W. S. Chan; Chia-Yin Chong; Yee-Sin Leo; Angela Li-Ping Chow; Paul Ananth Tambyah; et al. (Journal of NeuroVirology, 2015)

The interplay of sediment characteristics, depth, water temperature, and ocean currents shaping the biogeography of lancelets ( S ubphylum C ephalochordata) in the NW P acific waters - Hsiu‐Chin Lin; Jen‐Ping Chen; Benny K K Chan; Kwang‐Tsao Shao (Marine Ecology, 2015)
Lancelets (or amphioxus) are often found within the soft bottom of shallow tropical and temperate seas. The present study is the first to provide a fine‐scale biogeography of five species of lancelets ( A symmetron lucayanum , B ranchiostoma belcheri , B ranchiostoma japonicum , E pigonichthys cultellus , and E pigonichthys maldivensis ) in the NW Pacific and examine the effects of multiple environmental parameters. From multivariate analyses, the distribution and abundance patterns of lancelets were explained by a combination of factors comprising depth, temperature of the collecting month, mean temperature of the coldest month in the year, medium particle size and silt/clay ratio of the sediments. In addition, ocean currents also affect their distribution range. The major occurrence of A . lucayanum and E . maldivensis was associated with the warm K uroshio current, but E . maldivensis exhibited higher tolerance to low salinity and low temperature, and preferred substrata of slightly larger grain size, a lower ratio of suspended sediments, and deeper water. The closely related B . belcheri and B . japonicum exhibited fine‐scale habitat differentiation, and B . japonicum was abundant along the southern coast of C hina, where the salinity is lower in winter because of the C hina Coastal Current and the substratum is composed of very coarse sand with suspended sediments. Branchiostoma belcheri occurred in low abundance and was only recorded in N orthern T aiwan and the T aiwan Banks. Epigonichthys cultellus was found only at the T aiwan Banks, which had deep water, coarse sand, and a negligible amount of suspended sediments.

Polycyclic aromatic hydrocarbons associated with total suspended particles and surface soils in Kunming, China: distribution, possible sources, and cancer risks - Xiaoxia Yang; Dong Ren; Wenwen Sun; Xiaoman Li; Bin Huang; Rong Chen; Chan Lin; Xuejun Pan (Environmental Science and Pollution Research, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Clinical manifestations and prognostic factors of Morganella morganii bacteremia - T.-Y. Lin; M.-C. Chan; Y.-S. Yang; Y. Lee; K.-M. Yeh; J.-C. Lin; F.-Y. Chang (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Establishment of an Agrobacterium-mediated genetic transformation procedure for the experimental model orchid Erycina pusilla - Shu-Hong Lee; Chia-Wen Li; Chia-Hui Liau; Pao-Yi Chang; Li-Jen Liao; Choun-Sea Lin; Ming-Tsair Chan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Typhoon-enhanced upwelling and its influence on fishing activities in the southern East China Sea - Yi Chang; Jui-Wen Chan; Yuan-Chao Angelo Huang; Wei-Quan Lin; Ming-An Lee; Kuo-Tien Lee; Cheng-Hsin Liao; Kae-Yih Wang; Yi-Chun Kuo (International Journal of Remote Sensing, 2014)

Differential Regulation of Lipid Metabolism Genes in the Brain of Acetylcholinesterase Knockout Mice - Huang-Quan Lin; Yan Wang; Kam-Leung Chan; Tsz-Ming Ip; Chi-Cheong David Wan (Journal of Molecular Neuroscience, 2014)

Autolysis of krill protein from North Pacific krill Euphausia pacifica during protein recovery via isoelectric solubilization/precipitation - Le-Chang Sun; Yong-Lin Chen; Chan Zhong; Emiko Okazaki; Min-Jie Cao; Wu Yin Weng; Kazufumi Osako (Fisheries Science, 2014)

Progressive loss of striatal dopamine terminals in MPTP-induced acute parkinsonism in cynomolgus monkeys using vesicular monoamine transporter type 2 PET imaging ([18F]AV-133) - Yajing Liu; Feng Yue; Rongping Tang; Guoxian Tao; Xiaomei Pan; Lin Zhu; Hank F. Kung; Piu Chan (Neuroscience Bulletin, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Ruo-Chan Chen; Pan-Pan Yi; Rong-Rong Zhou; Mei-Fang Xiao; Ze-Bing Huang; Dao-Lin Tang; Yan Huang; Xue-Gong Fan (Molecular and Cellular Biochemistry, 2014)

Anti-apoptotic protein BRE/BRCC45 attenuates apoptosis through maintaining the expression of caspase inhibitor XIAP in mouse Lewis lung carcinoma D122 cells - Yiu-Loon Chui; Chun-Hung Ma; Wei Li; Zhenyu Xu; Yao Yao; Frances Ka-Yin Lin; John Yeuk-Hon Chan; Kenneth Ka-Ho Lee (Apoptosis, 2014)

First study on gene expression of cement proteins and potential adhesion-related genes of a membranous-based barnacle as revealed from Next-Generation Sequencing technology - Hsiu-Chin Lin; Yue Him Wong; Ling Ming Tsang; Ka Hou Chu; Pei-Yuan Qian; Benny K.K. Chan (Biofouling, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

pIMP-PH114 Carrying bla IMP-4 in a Klebsiella pneumoniae Strain is Closely Related to Other Multidrug-Resistant IncA/C2 Plasmids - Pak-Leung Ho; Wai-U Lo; Jane Chan; Yuk-Yam Cheung; Kin-Hung Chow; Wing-Cheong Yam; Chi-Ho Lin; Tak-Lun Que (Current Microbiology, 2014)

Relationship between road traffic noisescape and urban form in Hong Kong - Kin-Che Lam; Weichun Ma; Pak Kin Chan; Wing Chi Hui; King Lam Chung; Yi-tak Teresa Chung; Chun Yin Wong; Hui Lin (Environmental Monitoring and Assessment, 2013)

Biological response of high-back crucian carp (Carassius auratus) during different life stages to wastewater treatment plant effluent - Renmin Wang; Jingliang Liu; Xiaoxia Yang; Chan Lin; Bin Huang; Wei Jin; Xuejun Pan (Environmental Science and Pollution Research, 2013)

Molecular Characterization of an Atypical IncX3 Plasmid pKPC-NY79 Carrying bla KPC-2 in a Klebsiella pneumoniae - Pak-Leung Ho; Yuk-Yam Cheung; Wai-U Lo; Zhen Li; Kin-Hung Chow; Chi-Ho Lin; Jasper Fuk-Woo Chan; Vincent Chi-Chung Cheng (Current Microbiology, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Global transcriptome analysis and identification of a CONSTANS-like gene family in the orchid Erycina pusilla - Ming-Lun Chou; Ming-Che Shih; Ming-Tsair Chan; Shih-Yi Liao; Chen-Tran Hsu; Yao-Ting Haung; Jeremy J. W. Chen; Der-Chih Liao; Fu-Hui Wu; Choun-Sea Lin (Planta, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

The impact of low-frequency stimulation of subthalamic region on self-generated isometric contraction in patients with Parkinson’s disease - Chiung Chu Chen; Wey Yil Lin; Hsiao Lung Chan; Po Hsun Tu; Shih Tseng Lee; Chin Song Lu; Peter Brown (Experimental Brain Research, 2013)

Iodine content in commonly consumed food in Hong Kong and its changes due to cooking - Stephen Chung; Andy Chan; Ying Xiao; Violette Lin; Y.Y. Ho (Food Additives & Contaminants Part B-Surveillance, 2013)

Sex identification in the Collared Scops Owl (Otus bakkamoena) with novel markers generated by random amplified polymorphic DNA - P. H. Wang; H. A. Hsu; M. C. Chao; F. T. Chan; L. M. Wang; P. I. Lin; H. S. Tsao; H. W. Yuan; C. C. Chen; S. T. Ding (Conservation Genetics Resources, 2013)

The Effect of Osteochondral Regeneration Using Polymer Constructs and Continuous Passive Motion Therapy in the Lower Weight-Bearing Zone of Femoral Trocheal Groove in Rabbits - Nai-Jen Chang; Chih-Chan Lin; Chien-Feng Li; Kai Su; Ming-Long Yeh (Annals of Biomedical Engineering, 2013)

Stream discharge characteristics through urbanization gradient in Danshui River, Taiwan: perspectives from observation and simulation - Jr-Chuan Huang; Chun-Chiang Lin; Shih-Chien Chan; Tsung-Yu Lee; Shih-Chieh Hsu; Cheing-Tung Lee; Jiun-Chuan Lin (Environmental Monitoring and Assessment, 2012)

Heat-processed Gynostemma pentaphyllum extract improves obesity in ob/ob mice by activating AMP-activated protein kinase - Rehman Gauhar; Seung-Lark Hwang; Si-Sung Jeong; Ji-Eun Kim; Hebok Song; Dong Chan Park; Kyung-Sik Song; Tae Young Kim; Won Keun Oh; Tae-Lin Huh (Biotechnology Letters, 2012)

Novel ionic liquid supported-multicomponent reaction toward chimeric bis-heterocycles - Chih-Hau Chen; Chan-Yu Chen; Po-Tsung Lin; Chung-Ming Sun (Molecular Diversity, 2012)

Inhibition of Japanese Encephalitis Virus Infection by the Sulfated Polysaccharide Extracts from Ulva lactuca - Ya-Huang Chiu; Yi-Lin Chan; Tsung-Lin Li; Chang-Jer Wu (Marine Biotechnology, 2012)

Characterization of a new phage, termed ϕA318, which is specific for Vibrio alginolyticus - Ying-Rong Lin; Chi-Wen Chiu; Feng-Yi Chang; Chan-Shing Lin (Archives of Virology, 2012)

The Use of SU-8 Topographically Guided Microelectrode Array in Measuring Extracellular Field Potential Propagation - Jessica Ka-Yan Law; Chi-Kong Yeung; Lin Li; John Anthony Rudd; Sven Ingebrandt; Mansun Chan (Annals of Biomedical Engineering, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

In Vitro Toxicity Evaluation of 25-nm Anatase TiO2 Nanoparticles in Immortalized Keratinocyte Cells - Jin Chan; Tang Ying; Yang F. Guang; Li X. Lin; Tang Kai; Zhang Y. Fang; Ye X. Ting; Lin F. Xing; Yang Y. Ji (Biological Trace Element Research, 2011)

A rapid detection method for apoptosis and necrosis measurement using the Cellometer imaging cytometry - Leo Li-Ying Chan; Ning Lai; Elena Wang; Tim Smith; Xifeng Yang; Bo Lin (Apoptosis, 2011)

Novel ARF/p53-independent senescence pathways in cancer repression - Chia-Hsin Chan; Yuan Gao; Asad Moten; Hui-Kuan Lin (Journal of Molecular Medicine, 2011)

Detection and identification of a new phytoplasma associated with periwinkle leaf yellowing disease in Taiwan - Wuu-Yang Chen; Yao-Chen Huang; Meng-Lu Tsai; Chan-Pin Lin (Australasian Plant Pathology, 2011)

Mitochondrial proteomics analysis of tumorigenic and metastatic breast cancer markers - Yi-Wen Chen; Hsiu-Chuan Chou; Ping-Chiang Lyu; Hsien-Sheng Yin; Fang-Liang Huang; Wun-Shaing Wayne Chang; Chiao-Yuan Fan; I-Fan Tu; Tzu-Chia Lai; Szu-Ting Lin; Ying-Chieh Lu; Chieh-Lin Wu; et al. (Functional & Integrative Genomics, 2011)

Cellular Toxicity of TiO2 Nanoparticles in Anatase and Rutile Crystal Phase - Chan Jin; Ying Tang; F. Guang Yang; X. Lin Li; Shan Xu; X. Yan Fan; Y. Ying Huang; Y. Ji Yang (Biological Trace Element Research, 2011)

Manganese Superoxide Dismutase Deficiency Exacerbates Ischemic Brain Damage Under Hyperglycemic Conditions by Altering Autophagy - Suresh L. Mehta; Yanling Lin; Wenge Chen; Fengshan Yu; Luyi Cao; Qingping He; Pak H. Chan; P. Andy Li (Translational Stroke Research, 2011)

Change of air quality and its impact on atmospheric visibility in central-western Pearl River Delta - Jun-Ming Wan; Mang Lin; Chuen-Yu Chan; Zhi-Sheng Zhang; Guenter Engling; Xue-Mei Wang; Iat-Neng Chan; Shi-Yu Li (Environmental Monitoring and Assessment, 2011)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

Functional expression of the recombinant ATPase of orf virus - Fong-Yuan Lin; Kun-Wei Chan; Hsien-Chi Wang; Wei-Li Hsu; Min-Liang Wong (Archives of Virology, 2010)

Novel Vitamin and Gold-Loaded Nanofiber Facial Mask for Topical Delivery - Anahita Fathi-Azarbayjani; Lin Qun; Yew Weng Chan; Sui Yung Chan (AAPS PharmSciTech, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Identification of Flooding-Response Genes in Eggplant Roots by Suppression Subtractive Hybridization - Kuan-Hung Lin; Chun-Heng Lin; Ming-Tsir Chan; Hsiao-Feng Lo (Plant Molecular Biology Reporter, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Characterization of Burkholderia cepacia complex from cystic fibrosis patients in China and their chitosan susceptibility - Yuan Fang; Miao-miao Lou; Bin Li; Guan-Lin Xie; Fang Wang; Li-Xin Zhang; Yuan-Chan Luo (World Journal of Microbiology and Biotechnology, 2010)

Hawaiian Residents’ Preferences for Miconia Control Program Attributes Using Conjoint Choice Experiment and Latent Class Analysis - Catherine Chan-Halbrendt; Tun Lin; Fang Yang; Gwendalyn Sisior (Environmental Management, 2010)

Effect of the climate shift around mid 1970s on the relationship between wintertime Ural blocking circulation and East Asian climate - Lin Wang; Wen Chen; Wen Zhou; Johnny C. L. Chan; David Barriopedro; Ronghui Huang (International Journal of Climatology, 2010)
Blocking variability over the Ural Mountain region in the boreal winter and its relationship with the East Asian winter climate is investigated. The climate shift around mid 1970s has been shown to exert a significant influence on the blocking pattern. In contrast with the years before 1976/1977, the Ural blocking signal after 1976/1977 is found to propagate less into the stratosphere and more eastward in the troposphere to East Asia, which therefore exerts more influence on the East Asian winter climate. This enhanced Ural blocking–East Asian climate relationship amplifies the impact of Ural blocking on East Asia and, with the background of decreasing Ural blocking, contributes to the higher frequency of warm winters in this region. Further analyses suggest that the NAM‐related stratospheric polar vortex strength and its modulation on the propagation of atmospheric stationary waves can account for this change, with the key area being located in the North Atlantic region. Copyright © 2009 Royal Meteorological Society

Analysis of the mechanisms underlying the endothelium-dependent antivasoconstriction of puerarin in rat aorta - Li-Ping Yan; Yu-Lan Zhuang; Shun-Wan Chan; Shi-Lin Chen; Gang-Gang Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

A vitronectin M381T polymorphism increases risk of hemangioblastoma in patients with VHL gene defect - Jing-Shan Huang; Chih-Ming Lin; Yu-Che Cheng; Kun-Long Hung; Chih-Cheng Chien; Shao-Kuan Chen; Chih-Ju Chang; Chan-Wei Chen; Chi-Jung Huang (Journal of Molecular Medicine, 2009)

Isolation and characterization of microsatellite loci in the commercially important mudshrimp Austinogebia edulis (Upogebiidae) using PCR-based isolation of microsatellite arrays (PIMA) - Tzen-Yuh Chiang; Hung-Du Lin; Tin-Yam Chan; Cheng-Yu Hung; Feng-Jiau Lin (Conservation Genetics, 2008)

Role of the DxxDxD motif in the assembly and stability of betanodavirus particles - Yi-Min Wu; Chi-Hsin Hsu; Chun-Hsiung Wang; Wangta Liu; Wei-hau Chang; Chan-Shing Lin (Archives of Virology, 2008)

DC-SIGN and L-SIGN: the SIGNs for infection - Ui-Soon Khoo; Kelvin Y. K. Chan; Vera S. F. Chan; C. L. Steve Lin (Journal of Molecular Medicine, 2008)

Thiopurine S-methyltransferase activity in three major Asian populations: a population-based study in Singapore - Shirley Kow Yin Kham; Chin Kok Soh; Te Chih Liu; Yiong Huak Chan; Hany Ariffin; Poh Lin Tan; Allen Eng Juh Yeoh (European Journal of Clinical Pharmacology, 2008)

Transgene integration and organization in Cotton (Gossypium hirsutum L.) genome - Jun Zhang; Lin Cai; Jiaqin Cheng; Huizhu Mao; Xiaoping Fan; Zhaohong Meng; Ka Man Chan; Huijun Zhang; Jianfei Qi; Lianghui Ji; Yan Hong (Transgenic Research, 2008)

Comparative Physicochemical Characterization of Phospholipids Complex of Puerarin Formulated by Conventional and Supercritical Methods - Ying Li; Da-Jian Yang; Shi-Lin Chen; Si-Bao Chen; Albert Sun-Chi Chan (Pharmaceutical Research, 2008)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Streptomyces tritolerans sp. nov., a novel actinomycete isolated from soil in Karnataka, India - Dastager G. Syed; Dayanand Agasar; Chang-Jin Kim; Wen-Jun Li; Jae-Chan Lee; Dong-Jin Park; Li-Hua Xu; Xin-Peng Tian; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Fiber type and myosin heavy chain compositions of adult pretarsal orbicularis oculi muscle - Nai-Chen Cheng; Shu-Lang Liao; I-Jong Wang; I-Chan Lin; Yueh-Bih Tang (Journal of Molecular Histology, 2007)

Summer distribution and geochemical composition of suspended-particulate matter in the east china sea - Jia-Jang Hung; Chia-Lin Chan; Gong-Ching Gong (Journal of Oceanography, 2007)

Detection and identification of the phytoplasma associated with pear decline in Taiwan - Hsiu-Lin Liu; Ching-Chung Chen; Chan-Pin Lin (European Journal of Plant Pathology, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Pharmacogenomics of Phenolic Antioxidant Butylated Hydroxyanisole (BHA) in the Small Intestine and Liver of Nrf2 Knockout and C57BL/6J Mice - Sujit Nair; Changjiang Xu; Guoxiang Shen; Vidya Hebbar; Avantika Gopalakrishnan; Rong Hu; Mohit Raja Jain; Wen Lin; Young-Sam Keum; Celine Liew; Jefferson Y. Chan; Ah-Ng Tony Kong (Pharmaceutical Research, 2006)

Comparison of (−)-Epigallocatechin-3-Gallate Elicited Liver and Small Intestine Gene Expression Profiles Between C57BL/6J Mice and C57BL/6J/Nrf2 (−/−) Mice - Guoxiang Shen; Changjiang Xu; Rong Hu; Mohit R. Jain; Sujit Nair; Wen Lin; Chung S. Yang; Jefferson Y. Chan; A.-N. Tony Kong (Pharmaceutical Research, 2005)

Phylogenetic Analysis of Canine Parvovirus VP2 Gene in Taiwan - Hsien-Chi Wang; Wei-Da Chen; Shiun-Long Lin; Jacky Peng-Wen Chan; Min-Liang Wong (Virus Genes, 2005)

Gene stacking in Phalaenopsis orchid enhances dual tolerance to pathogen attack - Yuan-Li Chan; Kuang-Hung Lin; Sanjaya; Li-Jen Liao; Wen-Huei Chen; Ming-Tsair Chan (Transgenic Research, 2005)

The effect of salinity on trichloroethylene co-metabolism by mixed cultures enriched on phenol - Chi-Yuan Lee; Yu-Chia Chan; Chin-Lung Lin (World Journal of Microbiology and Biotechnology, 2005)

Expression of bioactive human interferon-gamma in transgenic rice cell suspension cultures - Tzy-Li Chen; Yi-Ling Lin; Yi-Ling Lee; Ning-Sun Yang; Ming-Tsair Chan (Transgenic Research, 2004)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

The mechanism of honokiol-induced and magnolol-induced inhibition on muscle contraction and Ca 2+ mobilization in rat uterus - Yu-Cheng Lu; Hwei-Hsien Chen; Chien-Hsin Ko; Yi-Ruu Lin; Ming-Huan Chan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Time-Frequency Analysis of Heart Rate Variability During Transient Segments - Hsiao-Lung Chan; Hui-Hsun Huang; Jiunn-Lee Lin (Annals of Biomedical Engineering, 2001)

Heterotrimeric G-protein and signal transduction in the nematode-trapping fungus Arthrobotrys dactyloides - Tsung-Hsien Chen; Chan-San Hsu; Pui-Jen Tsai; Yi-Feng Ho; Na-Sheng Lin (Planta, 2001)

A simple method to determine urea concentration using intact Helicobacter pylori and BromoCresol Purple as a pH indicator - Yuh-Ling Lin; Chien-Tsu Chen; Su-Cheng Lin; Cheng Lee; Hsien-Shou Kuo; Chun-Mean Shih; Yuan-Hsun Hsu; Yi-Ping Chin; Err-Cheng Chan (Biotechnology Letters, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Effects of recombinant lysostaphin on cytotoxicity and interleukin-8 level in normal human epidermal keratinocytes cell line - Err-Cheng Chan; C. Allen Chang; Tzong-Zeng Wu; Yuh-Ling Lin (Biotechnology Letters, 1998)

DNA probes and PCR primers for the detection of a phytoplasma associated with peanut witches'-broom - Miaw-Fan Chen; Chan-Pin Lin (European Journal of Plant Pathology, 1997)